Effects of yawed inflow on the dynamic performance of suction caisson-supported offshore wind turbines via wind tunnel tests - Yixiao Chen; Hongjun Liu; Kun Lin; Annan Zhou (Soil Dynamics and Earthquake Engineering, 2027)

Facilitating component separation and cascade resource utilization of sewer sludge using alkaline plant ash - Jiangbo Ding; Lei An; Yunfeng Liu; Hongjun Cui; Jun Wang; Rui Ma; Jinsuo Lu; Heliang Pang (Water Research, 2026)

Wet-spun weavable MXene/sodium alginate evaporator for efficient solar-driven water purification and concurrent power generation - Haofeng Liu; Jincheng Zhang; Shenao Wang; Weilin Xu; Huawang Zhao; Dongmao Ye; Hongjun Yang (Desalination, 2026)

In-situ fluorination reconstruction coupled with surface Sn-doping enables high-voltage fast-charging Li-rich Mn-based cathode - Meimei Yuan; Hongjun Liu; Fen Ran (Chemical Engineering Journal, 2026)

A novel two-layered hydroxyapatite-strengthened anammox-partial denitrification/anammox reactor for advanced nitrogen removal : Performance and mechanisms - Shenghao Ji; Hongjun Zhao; Shen Cui; Yujie Chen; Haojie Qin; Kengo Kubota; Jianyong Liu; Yu-You Li (Water Research, 2026)

Bisphenol a exposure induces low back pain associated with intervertebral disc degeneration via BIRC3-mediated nucleus pulposus cell senescence - Tao Kang; Hongjun Huang; Dun Liu; Junfei Feng; Yongqi Huang; Song Wang; Hongyuan Xu; Yuwang Du; Zuyuan Huang; Rongqing He; Hua Jiang (Toxicology and Applied Pharmacology, 2026)

Investigation on effect and mechanism of pullulan between flotation separation of chalcopyrite and pentlandite - Chunli Zhang; Jinfang Lv; Hongjun Fei; Haiyu Qian; Yitao Liu (Minerals Engineering, 2026)

Tire wear particles in the environment: A critical review on key challenges and future perspectives in fate, risk, and mitigation - Niling Zou; Hongjun Xiao; Gaoju Zou; Dehua Du; Zhen Liu; Shixin Zhang; Jiayue Zhu; Fan Yang; Kaifeng Wang; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

When and where do university-related travelers use ride-hailing? Evidence from 75 universities in Tianjin, China - Xinwei Ma; Jichi Zhao; Weijie Yu; Hongjun Cui; Yang Liu (Journal of Transport Geography, 2026)

Estimating daily evapotranspiration from remotely sensed instantaneous observations with surface flux equilibrium (SFE) theory and maximum entropy production (MEP) principle - Xin Pan; Zhanchuan Wang; Jinlong Shi; Yuanbo Liu; Zi Yang; Xu Ding; Suyi Liu; Hongjun Zhu; Congbao Zhu; Shile Yang; Yingbao Yang (Journal of Hydrology, 2026)

Extrusion-induced supramolecular disassembly of rice adjunct starch: governing enzymatic convertibility and fermentable sugar release in mashing - Lijun Jiang; Jialin Song; Mingming Qi; Jian Liu; Chengyi Sun; Bo Wang; Fengling Yue; Miaomiao Sui; Dongliang Zhang; Guihong Zhao; Hongjun Li (Food Chemistry, 2026)

Mass-flow control enhances nitrogen removal in a three-stage partial nitritation, anammox and partial denitrification/anammox system treating food waste digestate: Performance and N2O release characteristics - Shenghao Ji; Shen Cui; Hongjun Zhao; Haojie Qin; Tianyi Zhang; Yu Qin; Jianyong Liu; Yu-You Li (Environmental Research, 2026)

Mapping the True 3D Architecture: Quantitative Morphological Diversity of Human Hepatic Functional Unit Revealed by Fluorescence Micro-optical Section Tomography - Na Chen; Hongjun Liu; Xiaofeng Mei; Silin Liu; Hongjia Hu; Yunxi Lv; Qi Li; Wei Feng; Yifang Ping; Lu Zheng; Shiwu Dong; Yi Wu (Tissue and Cell, 2026)

Sludge-derived biochar-activated peroxymonosulfate as a waste-to-resource pretreatment for sustainable membrane fouling control: Adsorption-oxidation interplay and thermodynamic insights - Mingjing Xie; Biyan Wang; Jiaqi Liu; Xiao Xu; Hanmin Zhang; Meijia Zhang; Xiang Cai; Leihong Zhao; Bisheng Li; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Cleaner Production, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Construction of MOF-decorated 3D printed membrane with hierarchical surface functionalization for oil-water separation: Role of interfacial energy barrier - Jingtao Hu; Zhiyu Zhao; Hua Li; Saleem Raza; Ying Liu; Cheng Chen; Wei Yu; Yanchao Xu; Hongjun Lin; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2026)

Polystyrene microplastics induce auditory neurotoxicity in mammals: Integrated multi-omics profiling reveals oxidative damage and synaptic molecular dysregulation - Huanzhi Wan; Jingchun Liu; Xuan Yu; Ting Li; Wenting Yu; Bo Liu; Yingzhao Liu; Yuanyuan Zhang; Shimin Zong; Qingquan Hua; Hongjun Xiao (Journal of Hazardous Materials, 2026)

Efficient nutrient removal from low C/N municipal wastewater using a phototrophic biofilm system integrating simultaneous nitrification–denitrification and phosphorus removal (SND) - Qingan Meng; Wei Zeng; Jiayu Zhang; Hongjun Liu; Shuangshuang Li; Yongzhen Peng (Environmental Research, 2026)

Catechol-based synergistic antioxidant nanoplatform for alleviating cisplatin-induced hearing loss - Yunni Tu; Bo Liu; Congshu Feng; Yaqin Tu; Hang Yan; Zilong Chen; Jinghang Li; Youfa Wang; Hongjun Xiao; Lesan Yan (Chemical Engineering Journal, 2026)

Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Hydraulic Mechanism and Flow Pattern Optimization of Special Orthogonal Lateral-Intake Pumping Stations in Coastal Hydraulic Hubs - Jiawen Lu; Bin Xi; Wang Xi; Xuekun Hua; Hongjun Liu; Xuemei Xu (Journal of Marine Science and Engineering, 2026)
Special orthogonal lateral-intake pumping stations on coastal plains face severe lateral deflection and recirculation in the approach channel and forebay. Their underlying evolutionary mechanisms remain unclear, and conventional rectification methods cause substantial hydraulic losses. Using numerical simulations and hydraulic model experiments, this study investigates these unfavorable flow patterns and proposes an original Combined Arc-Frame Flow Straightening Structure (CAFS). This newly proposed CAFS differs from existing structures, achieving effective flow pattern improvement with reduced hydraulic loss. Results reveal three typical flow regimes—S-shaped mainstream, branching flow, and recirculation—and the flow field is partitioned into four hydrodynamic zones: the Mainstream Incident Zone, Mainstream Impact Zone, Mainstream Reflection Zone, and Low-Velocity Recirculation Zone. Axial velocity uniformity and flow angle are strongly influenced by lateral velocity, while turbulent kinetic energy exhibits intrinsic correlations with vertical vorticity. Lateral velocity, recirculation intensity, and hydraulic losses all increase positively with the Froude number. The CAFS effectively suppresses the low-velocity recirculation zone. Quantitative data show an improvement of 46.40 percentage points in uniformity of axial velocity distribution, a reduction of 0.157 rad (9°) in velocity-weighted average angle, 60.98% less turbulent dissipation, and 38.85% less total hydraulic loss. This study clarifies lateral-intake defect mechanisms and provides a valuable engineering reference.

Ultrasound-targeted cavitation induced tumor vascular normalization and radiotherapy sensitization in breast cancer - Zichao Liu; Huai Yang; Zenan Zhang; Chenke Kuang; Liyong Deng; Yueyong Li; Linyuan Jin; Hongjun Nie; Guihua Wang; Meng Du; Zhiyi Chen (Science China Life Sciences, 2026)

Grain tailoring enables robust high-temperature ferroelectricity in ultrathin Hf1–xZrxO2 films - Haoyu Lu; Yu Li; Liyang Ma; Geng Huangfu; Xuanyu Zhao; Changsong Xu; Hongjun Xiang; Yingfen Wei; Hao Jiang; Qi Liu; Ming Liu (Science Bulletin, 2026)

Tidal current-induced local scour around offshore tripile foundations: A CFD study of flow-structure-sediment interaction - Hongjun Liu; Wei He; Qi Yang; Lu Jing; Peng Yu; Xinyu Liu; Jieru Zhao (Ocean Engineering, 2026)

Flexible MOF nanosheet based membranes for high-flux antifouling oil/water separation and reverse cross-flow cleaning - Ting Gong; Jizheng Shang; Hongyuan Zhu; Yifan Liu; Hang Jiang; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Journal of Hazardous Materials, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Form-dependent chloroform adsorption behavior from powdered to sintered carbon - Qing Gao; Zhilong He; Jianjun Cheng; Jingwen Li; Dapeng Zhou; Jiahua Shi; Xiuli Chen; Hongjun Liu (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal differences in traffic efficiency and CO2 emissions across day types: A city-level data-driven analysis of cooperative vehicle-infrastructure systems - Bin Sun; Haoyu Xu; Zhaolang Wu; Qijun Zhang; Lin Wu; Yan Liu; Yanan Mi; Hongjun Mao (Journal of Environmental Management, 2026)

Tire wear particles induce a functional trade-off in bioretention systems: Coupled effects on nitrogen removal and greenhouse gas emissions - Gaoju Zou; Niling Zou; Yinghui Tang; Qinyi Wang; Hongjun Xiao; Quanhong Chen; Zhen Liu; Kaifeng Wang; Fan Yang; Huachao Zhao; Yu Qin; Anke Du; et al. (Environmental Research, 2026)

A multi-scale assessment of topographic anisotropy on Land Surface Emissivity and Temperature retrieval over the Yarlung Tsangpo River basin - Hongjun Zhu; Xin Pan; Shanhu Jiang; Xingwang Fan; Kevin Tansey; Zhenwei Wang; Rufat Guluzade; Matthew Payne; Jie Yuan; Suyi Liu; Zi Yang; Yingbao Yang (International Journal of Remote Sensing, 2026)

Influence of aspect ratio on the dynamic performance of suction caisson supported wind turbines: insights from wind tunnel tests - Yixiao Chen; Kun Lin; Annan Zhou; Hongjun Liu (Ocean Engineering, 2026)

Trade-off in bioretention: Tire wear particles mitigate sulfamethoxazole toxicity but exacerbate antibiotic resistance propagation - Quanhong Chen; Niling Zou; Yinghui Tang; Hongjun Xiao; Gaoju Zou; Kaifeng Wang; Jiayue Zhu; Zhen Liu; Dehua Du; Yu Qin; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

Targeting delivery of shikonin via cryo-shocked tumor cells for non-small cell lung cancer treatment - Huanhuan Huang; Hui Ren; Feiye Liu; Wenyue Lv; Mengzhen Xu; Huiheng Feng; Haoli Liu; Dong Chen; Peng Zhao; Hongjun Li; Jing Qin (Chemical Engineering Journal, 2026)

Unanswered questions on palmitic acid-driven neuroimmune inflammation in atopic dermatitis: a commentary on Chen et al. - Bo jiang; Hongjun Liu (Inflammation Research, 2026)

Impact of the green economic efficiency on industry-urban integration in the Yangtze River delta region - Mingtao Zhao; Xingpeng Liu; Hongjun Yuan; Lianbiao Cui; Xuebao Fu (Environment, Development and Sustainability, 2026)

Endothelialization of bioprosthetic valves: unanswered questions and a roadmap for translational research - Bo jiang; Hongjun Liu (Angiogenesis, 2026)

Bidirectional seismic kinematic coupling responses of large-diameter tunnels in sloping sites under Rayleigh waves: Analytical solutions using Green’s functions - Bin Li; Jiguo Liu; Yu Miao; Hongjun He (Tunnelling and Underground Space Technology, 2026)

A synergistic protective network of Polygonatum sibiricum-derived carbon nanoparticles against ethanol-induced and oxidative hepatic injury in HepG2 cells - Hongjun Jiang; Jiaxin Li; Qinxun Zhu; Xiongwei Liu; Xin Wei; Zuhua Wang; Ying Zhou; Tingting Feng (Tissue and Cell, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Synergistic integration of NiFe-MOF and carbon quantum dots for multifunctional nanofiltration membranes with high permeability and photocatalytic self-cleaning - Zhao Chen; Yifan Liu; Hongyuan Zhu; Haiyi Jin; Shasha Yuan; Die Ling Zhao; Hongjun Lin (Desalination, 2026)

PINCH proteins as dual-function nodes in vascular mural cell homeostasis: from cytoplasmic scaffolds to nuclear gatekeepers - Bo Jiang; Hongjun Liu (Angiogenesis, 2026)

A numerical study of damage evolution and crack propagation in backfill bodies of high-temperature thermal energy storage cavities in mines - Rui Zhan; Bo Zhang; Lang Liu; Chao Huan; Huisheng Qu; Huicong Xu; Jin Zhang; Hongjun Xi (Tunnelling and Underground Space Technology, 2026)

Deformation and dynamics of a flexible film attached to an elastically mounted circle cylinder under the unsteady vortices - Xinxin Liu; Hongjun Zhu; Wanhai Xu; Junlei Wang (Ocean Engineering, 2026)

Quantitative assessment impact of anthropogenic heat flux on global urban evapotranspiration retrieval at multiple temporal scales - Zi Yang; Xin Pan; Hongjun Zhu; Fanggang Li; Xiangjin Meng; Rufat Guluzade; Yuanbo Liu; Suyi Liu; Wen He; Zhenwei Wang; Yingbao Yang (Journal of Hydrology, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Impact of conservation tillage on maize growth dynamics in black soils of Northeast China through multi-platform remote sensing - Hongjun Liu; Junling Sun; Wei Wan; Shiwen Liu; Jianwei Li; Wei Lv; Zhong Liu (Field Crops Research, 2026)

Dynamic risk stratification in burn sepsis: methodological considerations and path forward - Bo Jiang; Hongjun Liu (Inflammation Research, 2026)

Improving GLASS AVHRR-derived terrestrial shortwave blue-sky albedo using GLASS MODIS-derived albedo: a global long-term study - Zi Yang; Hongjun Zhu; Jie Yuan; Rufat Guluzade; Xin Pan; Xu Ding; Suyi Liu; Congbao Zhu; Yuqian Li; Longlong Guo; Yingbao Yang (International Journal of Remote Sensing, 2026)

Wave-induced internal pumping as a sediment sorting mechanism and its implications for deltaic stratigraphic evolution: Insights from the Yellow River Delta - Shuyu Zhang; Jiewen Zheng; Pan Ji; Hongjun Zhang; Xiuhai Wang; Yonggang Jia; Xiaolei Liu (Sedimentary Geology, 2026)

Mineral-associated organic carbon promotes phosphorus accumulation in a long-term fertilized black soil - Naiyu ZHANG; Xiuzhi ZHANG; Yanhua CHEN; Lehlogonolo Abner MATELELE; Ping ZHU; Hongfang LIU; Xianmei ZHANG; Hongjun GAO; Gu FENG; Chang PENG; Shuxiang ZHANG (Pedosphere, 2026)

The startup characteristics of a one-stage PNA process under the Fe-free influent condition with iron-containing sludge as inoculum - Yan Guo; Qianqian Li; Hongjun Zhao; Hongzhi Ma; Xiaomin Liu; Jianguo Liu; Tianlong Zheng; Qunhui Wang; Yu-You Li (Journal of Water Process Engineering, 2026)

Decoding enhanced oily wastewater purification and photocatalytic self-cleaning performance of magnetic field-strategized composite membranes with surface-localized CoFe2O4@PDA - Yifan Liu; Hang Jiang; Hongyuan Zhu; Zhenyu Guo; Shasha Yuan; Liguo Shen; Die Ling Zhao; Hongjun Lin (Journal of Hazardous Materials, 2026)

Liquid fuel intrusion causes carbon canister deterioration and excess evaporative VOC emissions from in-use vehicles - Pengfei Song; Yan Liu; Qiang Chen; Jingyu Liu; Xueying Zeng; Tianlong Xing; Rui Zhang; Chongzhi Zhong; Taiyu Zhang; Ning Yang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Dynamic performance of suction caisson supported offshore wind turbines under different operational conditions - Kun Lin; Yixiao Chen; Annan Zhou; Hongjun Liu (Engineering Structures, 2026)

Bioaccumulation and trophic transfer of PAHs in the Yellow River Estuary food web: A fugacity-based model for ecological and human health risk assessment - Xin Liu; Xuguang Hong; Hongjun Song; Degang Wang; Kan Chen; Jiachen Sun; Zhaohui Zhang; Jiansong Chu (Marine Pollution Bulletin, 2026)

New insights into the characteristic flavor formation of Sichuan fermented sausages driven by liquid smoke addition: An integrated study based on microbiomics, flavoromics, and untargeted metabolomics - Dong Zhang; Xinrui Xie; Changlian Yu; Yuwei Liu; Li Yang; Chang Su; Xingzhong Zhang; Hongjun Li; Jie Tang (International Journal of Food Microbiology, 2026)

Interactions and binding mechanisms of soy protein isolate with theasinensin A in different pH conditions by multi-spectroscopy analysis and molecular docking - Haoyu Zhang; Weiqi Xu; Yulu Wang; Xia Fan; Qiankun Guo; Hongjun Liu; Jialu Ao; Tianjin Sun; Muhammad Abid; Xiaoxiong Zeng (Food Chemistry, 2026)

Microstructure-engineered NiFe-LDH composite membranes integrating high flux with visible-light-driven self-regeneration for sustainable treatment of complex oily water - Hongyuan Zhu; Yifan Liu; Shasha Yuan; Liguo Shen; Hongjun Lin; Sui Zhang; Die Ling Zhao (Desalination, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Spatiotemporal patterns of super-emitting diesel vehicles: A scalable remote sensing framework for urban emission hotspot mitigation - Junxia Gao; Yan Liu; Ning Yang; Zeping Cao; Jing Zhao; Lin Wu; Wentian Xu; Binfeng Yan; Zhengyu Jia; Hongjun Mao (Atmospheric Pollution Research, 2026)

Mechanical and economic performance of geogrid-reinforced base pavements: An integrated numerical, experimental, and field study - Qian Liu; Hongjun Jing; Di Wang (Geotextiles and Geomembranes, 2026)

Triatomic-doped MXene based catalyst with sodium alginate encapsulation their molecular and DFT calculation study for efficient photocatalytic removal of disinfected by-product from drinking water - Saleem Raza; Ata Ur Rehman; Zhiyu Zhao; Hua Li; Cheng Chen; Wei Yu; Ying Liu; Yanchao Xu; Liguo Shen; Hongjun Lin (Chemical Engineering Journal, 2026)

Metagenomic insights into the survival strategy of Tetrasphaera under prolonged anaerobic conditions: transition from polyphosphate metabolism to fermentation - Zhaoyang Bi; Wei Zeng; Hongjun Liu; Jiayu Zhang; Wenzhuo Jiang; Yongzhen Peng (Chemical Engineering Journal, 2026)

Revealing denitrifying phosphorus removal metabolic diversity and FNA tolerance of Tetrasphaera with nitrate and nitrite as electron acceptors - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Yao Lu; Zhaoyang Bi; Yongzhen Peng (Chemical Engineering Journal, 2026)

Open the door to the new world of singlet oxygen in the peracetic acid system: Generation and identification - Rui Liu; Wen Lu; Yuting Liu; Mingzhu Zhou; Bisheng Li; Hongjun Lin; Jiaheng Teng; Liguo Shen; Xiaohong Guan; Leihong Zhao (Water Research, 2026)

Multiscale thermodynamic insights into membrane fouling control by biochar-activated peroxymonosulfate pretreatment: Synergy of oxidation and adsorption - Mingjing Xie; Wenfa Yang; Xiaoni Zhou; Biyan Wang; Jiaqi Liu; Xiao Xu; Liguo Shen; Hanmin Zhang; Meijia Zhang; Wei Yu; Jiaheng Teng; Hongjun Lin; et al. (Water Research, 2026)

Unveiling the microplastic migration behavior in riverine systems: hydrodynamic impacts on transport and sedimentation - Kaifeng Wang; Quanhong Chen; Qiming Cheng; Yuqing Tan; Wenyu Xiao; Yihong Su; Fei Liu; Hongjun Xiao; Ye Rao; Zhen Liu; Yao Chen (Journal of Hydrology, 2026)

Electroactivated cobalt-cobalt Prussian blue analog composite membrane for rapid persulfate-driven antibiotic degradation and fouling mitigation - Xiaoyue Yao; Hao Wang; Jingjing Liu; Yu Wang; Xuewen Tang; Hongjun Lin; Leihong Zhao; Bisheng Li; Renjie Li (Chemical Engineering Journal, 2026)

Unraveling synergistic CO2 binding in anion-pillared materials and amine-modified MOFs for direct air capture (DAC) via combined DFT-D3 calculation and PALS experiment - Niu Liu; Dongfang Guo; Shiwang Gao; Hanming Liu; Hongwei Niu; Lianbo Liu; Shiqing Wang; Qi Wang; Huanjun Wang; Wei Xu; Hongjun Zhang (Chemical Engineering Journal, 2026)

Robust trajectory tracking control of lunar rovers considering wheel-terrain slip - Yuzhe Xu; Hongjun Xing; Yanqing Liu; Jinyao Zhu; Jinbao Chen; Liang Ding (Advances in Space Research, 2026)

Evolving Collective Intelligence for Unmanned Marine Vehicle Swarms: A Federated Meta-Learning Framework for Cross-Fleet Planning and Control - Yuhan Ye; Hongjun Tian; Yijie Yin; Yuhan Zhou; Yang Xiong; Zi Wang; Yaojiang Liu; Zinan Nie; Zitong Zhang; Yichen Wang; Jingyu Sun (Journal of Marine Science and Engineering, 2025)
The development of robust autonomous maritime systems is fundamentally constrained by the “data silo” problem, where valuable operational data from disparate fleets remain isolated due to privacy concerns, severely limiting the scalability of general-purpose navigation intelligence. To address this barrier, we propose a novel Federated Meta-Transfer Learning (FMTL) framework that enables collaborative evolution of unmanned surface vehicle (USV) swarms while preserving data privacy. Our hierarchical approach orchestrates three synergistic stages: (1) transfer learning pre-trains a universal “Sea-Sense” foundation model on large-scale maritime data to establish fundamental navigation priors; (2) federated learning enables decentralized fleets to collaboratively refine this model through encrypted gradient aggregation, forming a distributed cognitive network; (3) meta-learning allows for rapid personalization to individual vessel dynamics with minimal adaptation trials. Comprehensive simulations across heterogeneous fleet distributions demonstrate that our federated model achieves a 95.4% average success rate across diverse maritime scenarios, significantly outperforming isolated specialist models (63.9–73.1%), while enabling zero-shot performance of 78.5% and few-shot adaptation within 8–12 episodes on unseen tasks. This work establishes a scalable, privacy-preserving paradigm for collective maritime intelligence through swarm-based learning.

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Effect of pipe-wall gap ratio on the flow-induced vibration of a submarine pipe span conveying flow - Hongjun Zhu; Tianhao Wu; Shida Liu; Tongming Zhou (Ocean Engineering, 2025)

Experimental investigation of the hydrodynamic response of a cantilevered gas-conveying flexible tube - Hongjun Zhu; Peng Liu; Yue Gao; Lin Ding; Tongming Zhou (Ocean Engineering, 2025)

Enhanced built-in electric field and strong interfacial electronic coupling in 2D/2D BiO2-x/Ti3C2 Schottky heterojunction boost exciton dissociation for sustainable molecular oxygen activation toward 100 % singlet oxygen generation - Chongyang Yang; Song Tian; Yanyan Liu; Liguo Shen; Cheng Chen; Yanchao Xu; Leihong Zhao; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Submarine groundwater discharge derived metal elements fluxes in a seawater intrusion influenced area - Yancheng Wang; Guangquan Chen; Wenzhe Lyu; Xinbin Zhao; Chutima Boonyaridsripong; Shengfa Liu; Hongjun Yu; Xingyong Xu (Journal of Environmental Sciences, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Pulse electrodeposition of graphene/copper composite foils from waste printed circuit board leachate - Yan Sun; Yamin Li; Jingyu Zhang; Hongjun Liu (Chemical Engineering Journal, 2025)

MAZ-mediated LAMA5 transcription activation promotes gastric cancer progression through the STAT3 signaling - Yu Wang; Jiazhong Xu; Hongxia Zhang; Xiaobo Guo; Hongjun Liu; Qinhui Sun (Functional & Integrative Genomics, 2025)

Evaluation of feeding intensity in pearl gentian grouper under factory aquaculture environment based on multi-feature fusion and MDGSNet model - Zeshuang Ma; Hongpo Wang; Hong Zhou; Yunchen Tian; Jianing Quan; Haohui Liu; Zhanshuo Sun; Hongjun Yang (Aquaculture International, 2025)

Decoupling and decomposition analysis of industrial carbon emissions, and projection of its future trends: A case study of Quanzhou, China - Yanxi Tang; Jing Xu; Muping Shen; Jiachang Zuo; Fengyi Yu; Yingmao Tang; Tingting Liu; Hongjun Jin; Yongjin Luo; Qingrong Qian; Qinghua Chen (Environment, Development and Sustainability, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Widely targeted metabolomics and GC–IMS reveal flavor and metabolite variations in Rex and Hyla rabbit meat under different cooking methods - Shuyun Liu; Hongjun Li; Bin Wen; Li Yang; Xuelian Sun; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

Efficient preparation and structural characterization of theabrownins from fermented summer green tea with Aspergillus cristatus (MK346334) in submerged fermentation - Jingqian Zheng; Jiayue Fang; Hongjun Liu; Zhiyong Xie; Xia Fan; Guijie Chen; Xiaoxiong Zeng (Food Chemistry, 2025)

A source-oriented precise risk assessment of trace metal(loid)s in sediments of the Yangtze River Basin - Kuo Pang; Lu Liu; Junlan Yang; Hongjun Zhao; Wei Hu; Xiaonan Ji; Yali Guo; Min Li (Environmental Pollution, 2025)

A graded E-shaped piezoelectric energy harvester for ultra-broadband and high-capability energy harvesting - Pingping Liu; Hongjun Xiang; Bao Zhao (Engineering Structures, 2025)

Diatomic catalytic sites on MOF-derived architecture towards effective H2 production - Hongjun Dong; Hansong Cheng; Yun Wang; Zuoyi Liu; Deping Wang; Liqiu Zhang; Yangyang Yu; Chunmei Li (Chemical Engineering Journal, 2025)

Magnetically directed interfacial polyamerization of Fe3O4@CdS@CQDs-embedded polyamide nanofiltration membranes with enhanced separation and photocatalytic self-cleaning performance - Erqiao Chen; Zhihao Chen; Zhongting Liu; Mingzhu Zhou; Bisheng Li; Renjie Li; Liguo Shen; Yang Jiao; Hongjun Lin; Yanchao Xu (Chemical Engineering Journal, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

Unveiling the role of N-doped carbon quantum dots in relieving humic acid inhibition and promoting methanogenesis via enhanced electron transfer - Qiang Liu; Mahmoud Mazarji; Yeqing Li; Lu Feng; Hongjun Zhou; Quan Xu; Alastair James Ward; Yajing Wang; Jianping Su; Chunming Xu; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Refinement of vehicle emission factor estimation in tunnel experiments using CFD and field measurement - Xiaoyu Liang; Jianfei Peng; Yan Liu; Jinsheng Zhang; Lin Wu; Hongjun Mao (Environmental Pollution, 2025)

Insights into synergistic metabolism mechanisms of carbon, nitrogen and phosphorus in Tetrasphaera-dominated partial denitrifying phosphorus removal and anammox (PDPRA) process - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Yao Lu; Shuangshuang Li; Yongzhen Peng (Water Research, 2025)

Consortia of SQR9 mutant strains containing the luxS gene mutation can maintain higher functional stability than the wild type - Jingjing WANG; Lingxue MENG; Ying ZENG; Xinrui ZHU; Chuanyong TANG; Zhihui XU; Hongjun LIU; Rong LI; Qirong SHEN (Pedosphere, 2025)

Hybrid machine learning model with SHAP interpretability for optimization of targeted nitrogen and phosphorus removal from bioretention systems - Ying Yuan; Quanhong Chen; Yinghui Tang; Qiming Cheng; Gaoju Zou; Xiaoke Lian; Zhen Liu; Hongjun Xiao; Mingyue Liu; Kaifeng Wang; Shixin Zhang; Yao Chen (Journal of Water Process Engineering, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Competitive effects and environmental factors driving heavy metal leaching in stabilized municipal solid waste incineration fly ash under extreme conditions - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Chuanfu Wu; Shu Liu (Journal of Hazardous Materials, 2025)

Mimicking butterflies: Thermal adaptive management material with shape memory Janus arrays - Guangyao Hou; Xinzhi Wang; Henghao Liu; Hongjun Kang; Xin Jia; Yang Li; Wei Qin; Xiaohong Wu (Chemical Engineering Journal, 2025)

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Spatiotemporal Meta-Reinforcement Learning for Multi-USV Adversarial Games Using a Hybrid GAT-Transformer - Yang Xiong; Shangwen Wang; Hongjun Tian; Guijie Liu; Zihao Shan; Yijie Yin; Jun Tao; Haonan Ye; Ying Tang (Journal of Marine Science and Engineering, 2025)
Coordinating Multi-Unmanned Surface Vehicle (USV) swarms in complex, adversarial maritime environments is a significant challenge, as existing multi-agent reinforcement learning (MARL) methods often fail to capture intricate spatiotemporal dependencies, leading to suboptimal policies. To address this, we propose Adv-TransAC, a novel Spatio-Temporal Meta-Reinforcement Learning framework. Its core innovation is a hybrid GAT-transformer architecture that decouples spatial and temporal reasoning: a Graph Attention Network (GAT) models instantaneous tactical formations, while a transformer analyzes their temporal evolution to infer intent. This is combined with an adversarial meta-learning mechanism to enable rapid adaptation to opponent tactics. In high-fidelity escort and defense simulations, Adv-TransAC significantly outperforms state-of-the-art MARL baselines in task success rate and policy robustness. The learned policies demonstrate the emergence of complex cooperative behaviors, such as intelligent risk-aware coordination and proactive interception maneuvers. The framework’s practicality is further validated by a communication-efficient federated optimization architecture. By effectively modeling spatiotemporal dynamics and enabling rapid adaptation, Adv-TransAC provides a powerful solution that moves beyond reactive decision-making, establishing a strong foundation for next-generation, intelligent maritime platforms.

Bio-derived carboxymethyl cellulose-graft-gallic acid antiscalant with remarkable antibacterial activity for reverse osmosis scaling and biofouling control - Liping Xiong; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Liguo Shen (Water Research, 2025)

Rice-fish coculture without phosphorus addition improves phosphorus availability in paddy soil by regulating phosphorus fraction partitioning and alkaline phosphomonoesterase-encoding bacterial community - Xing LIU; Yuting CHEN; Hongjun ZHENG; Daolin SUN; Jiaen ZHANG; Qi JIA; Qi CHEN (Pedosphere, 2025)

Reconstructing missing NOx emissions in heavy-duty diesel vehicle OBD data: A machine learning approach - Zeping Cao; Yanan Wang; Xiaoyang Zhao; Jiawei Yin; Zhenyu Jia; Yanjie Zhan; Yan Liu; Qijun Zhang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Reversing inhibition to promotion in phenol-ammonium metabolism via algal-microbial fuel cell: Mechanisms of phenol-ammonium interaction and synergistic removal - Yaqi Liu; Mengqi Zheng; Longyi Lv; Guowei Chen; Chengye Wang; Zhenhu Hu; Jingwei Feng; Binghan Xie; Hongjun Han; Wei Wang (Journal of Hazardous Materials, 2025)

Rhubarb with Different Cooking Methods Restored the Gut Microbiota Dysbiosis and SCFAs in Ischemic Stroke Mice - Jing Xu; Taotao Liu; Fuzhu Pan; Xuan Ao; Lan Wang; Rixin Liang; Yuxin Lei; Yurong Ding; Miao Yu; Li Li; Hongjun Yang (Molecular Neurobiology, 2025)

Study on climate suitability for maize and technical implementation strategies under conservation tillage in Northeast China - Hongjun Liu; Wei Wan; Mandi Zheng; Jianwei Li; Shiwen Liu; Wei Lv; Yongxin Zhou; Zhong Liu (Soil and Tillage Research, 2025)

Cu-Thioamide coordination polymers derived Cu-S catalysts for CO2 electroreduction to formate - Honglin Li; Xin Zhang; Yuanyuan Wen; Jingyuan Li; Yu Liu; Hongjun Mao; Hongman Sun; Jingbin Zeng; Zifeng Yan (Fuel, 2025)

Application of construction waste residue-based compositing fillers in bioretention facility: Intensified nitrogen removal and mitigated by-product effects - Xiaoke Lian; Yinghui Tang; Qiong Wu; Hongjun Xiao; Jianhua Ni; Ying Yuan; Qiyi Wang; Zhen Liu; Gaoju Zou; Shixin Zhang; Chaohan Meng; Yao Chen (Environmental Research, 2025)

Tea tree oil Pickering emulsions stabilized by sodium lignosulfonate-zein covalent conjugate for fungicide delivery and enhanced control efficacy against peanut sclerotium blight - Jihao Zuo; Yitong Lin; Jiayuan Tian; Jinting Cai; Li Hao; Dongjie Liu; Qin Wang; Gengsheng Xiao; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2025)

Ensemble predictions of high trophic-level fish distribution and species association in response to climate change in the coastal waters of China - Jiao Wang; Xiaohan Liu; Xiuxia Mu; Hongjun Li; Baoquan Li; Yunlei Zhang (Marine Pollution Bulletin, 2025)

Natural variations in the promoter of ZmDeSI2 encoding a deSUMOylating isopeptidase controls kernel methionine content in maize - Xin Lu; Yuhong Lei; Zhennan Xu; Zixiang Cheng; Meng Liu; Yuxin Tai; Xiaohua Han; Zhuanfang Hao; Mingshun Li; Degui Zhang; Hongjun Yong; Jienan Han; et al. (Molecular Plant, 2025)

Integrated process of Tetrasphaera-dominated enhanced biological phosphorus removal and sulfur autotrophic denitrification in a single reactor to treat VFAs-free wastewater: Feasibility, performance and mechanism - Hongjun Liu; Wei Zeng; Gangxin Chen; Qingan Meng; Jiayu Zhang; Zhaoyang Bi; Yongzhen Peng (Journal of Water Process Engineering, 2025)

Exploring the regulation of metabolic changes mediated by different combined starter cultures on the characteristic flavor compounds and quality of Sichuan-style fermented sausages - Buzhou Xu; Wenliang Qiu; Yuwei Liu; Fanyi Gong; Qian Liu; Jiaxin Chen; Yong Tang; Chang Su; Jie Tang; Dong Zhang; Hongjun Li (Food Research International, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Correction: Thioredoxin-1 Protects Neurons Through Inhibiting NLRP1-Mediated Neuronal Pyroptosis in Models of Alzheimer’s Disease - Jinjing Jia; Hongjun Liu; Liyan Sun; Yunfeng Xu; Xiansi Zeng (Molecular Neurobiology, 2025)

Correction: Thioredoxin-1 Protects Neurons Through Inhibiting NLRP1-Mediated Neuronal Pyroptosis in Models of Alzheimer’s Disease - Jinjing Jia; Hongjun Liu; Liyan Sun; Yunfeng Xu; Xiansi Zeng (Molecular Neurobiology, 2025)

SIRT3 regulates PFKFB3-mediated glycolysis to attenuate cisplatin-induced ototoxicity both in vivo and in vitro - Wei Tang; Shimin Zong; Peiyu Du; Xuan Yu; Ting Li; Bo Liu; Yu Zhong; Wenyang Lei; Wenting Yu; Hongjun Xiao (Archives of Toxicology, 2025)

Fluxapyroxad induces chronic colonic inflammation via inhibiting intestinal aryl hydrocarbon receptors in mice - Yue Cao; Shouchun Xiao; Yaofeng Fang; Jiaxing Yang; Zeyu Hu; Hongjun Zhang; Xueke Liu; Donghui Liu; Zhiqiang Zhou; Peng Wang (Science of The Total Environment, 2025)

Advanced three-dimensional numerical simulation on influence of MS2AF on scour protection considering seabed response: A coupled CFD-FEM method - Chenghao Zhu; Xinyu Liu; Qi Yang; Wenkun Zang; Hongjun Liu; Xiaolong Liu (Ocean Engineering, 2025)

Flow-induced vibrations of a wake cylinder at a low mass-damping ratio - Jian Liu; Md. Mahbub Alam; Hongjun Zhu; Md Islam; Yu Zhou; Mostafa Zeinoddini (Ocean Engineering, 2025)

L-cysteine modulates the Maillard reaction: Impacts on PhIP and pyrazine formation - Xiaoran Chu; Pengfei Du; Weiting Wang; Hongjun He; Peng Hu; Yaobo Liu; Min Li; Wenxiang Jiang; A.M. Abd El-Aty (Food Chemistry, 2025)

Mechanical Properties and Microstructure Characteristics of Submerged Cement-Based Stabilized Marine Soft Clay Enhanced with ISS and PAM - Chenghao Zhu; Peng Yu; Zixian Guo; Qigang Wang; Hongjun Liu (Journal of Ocean University of China, 2025)

O-GlcNAc transferase promotes synaptic assembly independent of catalytic activity in C. elegans - Mengting Wu; Huihui Jiang; Qian Li; Yunhe Liu; Hongjun Zhang; Zhiyong Shao (Journal of Biosciences, 2025)

Multifactorial Controls on the Dongdaobei Submarine Canyon System, Xisha Sea, South China Sea - Meijing Sun; Hongjun Chen; Chupeng Yang; Xiaosan Hu; Jie Liu (Journal of Marine Science and Engineering, 2025)
The submarine canyons system is the most widely distributed geomorphic unit on the global continental margin. It is an important concept in the field of deep-water sedimentation and geohazards. Based on high-resolution multibeam bathymetry and two-dimensional seismic data, the dendritic canyon system north of Dongdao island is studied at the eastern Xisha area of the South China Sea. The Dongdaobei submarine canyon is distributed in water depths between 1000 and 3150 m. The main source area in the upper course of the canyon originates from the northwest of Dongdao platform and the Yongxing platform. The sediments from the source area are transported to the main canyon in the form of various gravity flows. Landslides on the slope significantly impact canyon evolution by delivering sediment to the canyon head and causing channel deflection through substrate failure and flow-path reorganization. A large number of pockmarks are distributed around the north slope of the main canyon. The small-scale channels, which are formed as a result of the continuous erosion of the pockmark chains, are connected to the canyon sidewalls. The seamounts are distributed along the south bank of the canyon, exerting a controlling influence on the directional changes in the main canyon’s downstream segment. The formation and evolution of the Dongdaobei submarine canyon are primarily influenced by several factors, including tectonic activity and inherited negative topography, erosion by sedimentary gravity flows, sediment instability, and the shielding effect of seamounts.

Microstructural regulation of Ir(III) complexes for enhanced photocytotoxicity in photodynamic cancer therapy - Xiaomeng Liu; Qing Zhang; Jiaqi Li; Zhewen Deng; Senqiang Zhu; Bo Ma; Rui Liu; Hongjun Zhu (Journal of Photochemistry and Photobiology B: Biology, 2025)

A comprehensive OBD data analysis framework: Identification and factor analysis of high-emission heavy-duty vehicles - Zeping Cao; Kai Shi; Hao Qin; Zhou Xu; Xiaoyang Zhao; Jiawei Yin; Zhenyu Jia; Yanjie Zhang; Hailiang Liu; Qijun Zhang; Hongjun Mao (Environmental Pollution, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

A study of tripartite strategies for closed-loop charging infrastructure construction of new energy vehicles in China under the expectation of government withdrawal subsidies - Chengyu Li; Xibin Lu; Yiqing Liu; Zuhui Xia; Xueni Wang; Hongjun Zhao (Journal of Cleaner Production, 2025)

A Model for apparent permeability of organic slit nanopores in shale gas based on GCMC molecular simulation - Yi Zhang; Bin Zhang; Banghua Liu; Jie Liu; Qiansheng Wei; Hongjun Lu; Pengyu Zhu; Rui Wang; Yongli Yan (Fuel, 2025)

Impact of flow velocity on growth performance, muscle texture, and nutritional composition in seabass (Lateolabrax maculatus) - Fan Fei; Yingying Fang; Zhiwen Zhu; Xinyu Liu; Ao Li; Jiawen Zhang; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Wensheng Li; Chuanxin Zhang; Baoliang Liu (Aquaculture International, 2025)

Strengthening peroxymonosulfate activation via cotton-derived carbon: Pathway transformation from radical to non-radical - Runbin Su; Yonglin Ma; Lei Liu; Qiangshun Wu; Du Fu; Yu Li; Hongjun Lin; Xiaoxuan Wei; Muhammad Saboor Siddique; Jianrong Chen; Xi-Lin Wu (Journal of Cleaner Production, 2025)

Spatiotemporal distribution prediction for PM2.5 based on STXGBoost model and high-density monitoring sensors in Zhengzhou High Tech Zone, China - Shiqi Zhao; Hong Lin; Hongjun Wang; Gege Liu; Xiaoning Wang; Kailun Du; Ge Ren (Journal of Environmental Management, 2025)

Astral-based DIA proteomics explored the flavor enhancement mechanism of Chinese traditional smoked bacon by staphylococcal co-fermentation - Li Yang; Hongjun Li; Han Wu; Xueling Sun; Shuyun Liu; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Extent of As(III) versus As(V) adsorption on iron (oxyhydr) oxides depends on the presence of vacancy cluster-like micropore sites: Insights into a seesaw effect - Juan Liu; Yixin Duan; Hao Chen; Bangjiao Ye; Hongjun Zhang; Wenfeng Tan; Andreas Kappler; Jingtao Hou (Science of The Total Environment, 2024)

Advancing anaerobic digestion with MnO2-modified biochar: Insights into performance and mechanisms - Yeqing Li; Jinglei Zhang; Xinran Wen; Mahmoud Mazarji; Shuo Chen; Qiang Liu; Shenggeng Zhao; Lu Feng; Gang Li; Hongjun Zhou; Junting Pan (Science of The Total Environment, 2024)

Soil nutrient levels are associated with suppression of banana Fusarium wilt disease - Yifan Cao; Yannan Ou; Nana Lv; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Soil Ecology Letters, 2024)

Indication of Deep-Water Gravity Flow Types by Shelf-Edge Trajectory Migration Patterns: A Case Study of the Quaternary Qiongdongnan Basin, South China Sea - Chang Ma; Hongjun Qu; Xian Liu (Journal of Marine Science and Engineering, 2024)
The shelf-edge trajectory is comprehensively controlled by tectonics, sediment supply, sea level, and climate fluctuations; its migration and evolution have a strong influence on what happens in the deep-water depositional system during the Quaternary. The shelf-edge trajectory pattern, sediment-budget partitioning into deep-water areas, and reservoir evaluations are focused topics in international geosciences. In this paper, the Qiongdongnan Basin (QDNB) in the northern South China Sea is taken as an example to study how shelf-edge trajectory migration patterns can influence the types of deep-water gravity flow which are triggered there. Through quantitatively delineating the Quaternary shelf-edge trajectory in the QDNB, four types of shelf-edge trajectory are identified, including low angle slow rising type, medium angle rising type, high angle sharp rising type, and retrogradation-slump type. A new sequence stratigraphic framework based on the migration pattern of shelf-edge trajectory is established. There are four (third-order) sequences in the Quaternary, and several systems tracts named lowstand systems tract (LST), transgressive systems tract (TST), and highstand system tract (HST) are identified. This study indicates that the type of deep-water gravity flow can be dominated by the shelf-edge trajectory migration patterns. When the shelf-edge trajectory angle (α) ranged between 0° and 4°, the continental canyons were mostly small-scaled and shallowly incised, with multiple large-scale sandy submarine fan deposits with few MTDs found in the deep-water area. When the angle (α) ranged from 4°

Polyimide-multiwalled carbon nanotubes composite as electrochemical sensing platform for the simultaneous detection of nitrophenol isomers - Jianzheng Wang; Chunying Liu; Ziao Di; Jiayu Huang; Hongjun Wei; Minjie Guo; Xiaoliang Yu; Nan Li; Jin Zhao; Bowen Cheng (Chemosphere, 2024)

Sequence stratigraphy driven by tectonic subsidence and astronomical forcing: A case study from the Miocene Pearl River Mouth Basin, South China Sea - Xian Liu; Jiawang Ge; Hongjun Qu; Chang Ma (Marine and Petroleum Geology, 2024)

Enhanced removal of quinoline and nitrate in synthetic photovoltaic wastewater by non-aerating algae-bacteria symbiosis system: Microbial environmental response and nitrogen metabolism - Zipeng Yan; Mengqi Zheng; Yan Wang; Hao Shen; Yaqi Liu; Jie Wang; Hong Mei; Yuying Du; Yantao Zhou; Kuizu Su; Hongjun Han (Journal of Water Process Engineering, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

A negative-carbon planning method for agricultural rural industrial park integrated energy system considering biomass energy and modern agricultural facilities - Dewei Jiang; Hongjun Gao; Shuaijia He; Yuan Huang; Junyong Liu (Journal of Cleaner Production, 2024)

High-efficient synthesis of straw-derived carbon quantum dots for facilitating methanogenic performance in high-load co-digestion of food waste and excess sludge - Qiang Liu; Haoyu Zhang; Haozhen Wang; Shenggeng Zhao; Yeqing Li; Lu Feng; Junting Pan; Hongjun Zhou; Chunming Xu (Chemical Engineering Journal, 2024)

Integrated process of Tetrasphaera-dominated in-situ waste activated sludge fermentation, biological phosphorus removal and endogenous denitrification in single reactor for treatment of wastewater with limited carbon sources - Hongjun Liu; Wei Zeng; Lei Wu; Qingan Meng; Jiayu Zhang; Yongzhen Peng (Bioresource Technology, 2024)

Thioredoxin-1 Protects Neurons Through Inhibiting NLRP1-Mediated Neuronal Pyroptosis in Models of Alzheimer’s Disease - Jinjing Jia; Hongjun Liu; Liyan Sun; Yunfeng Xu; Xiansi Zeng (Molecular Neurobiology, 2024)

Response of food waste anaerobic digestion to the dimensions of micron-biochar under 30 g VS/L organic loading rate: Focus on gas production and microbial community structure - Qiang Liu; Ziyan Sun; Junting Pan; Lu Feng; Hongjun Zhou; Yeqing Li; Gang Li (Chemosphere, 2024)

Exploring source-specific ecological risks of PAHs near oil platforms in the Yellow River Estuary, Bohai Sea - Xin Liu; Xuguang Hong; Hongjun Song; Tong Zhang; Kan Chen; Jiansong Chu (Marine Pollution Bulletin, 2024)

Numerical investigation of the vortex-induced vibration of a circular cylinder in oscillatory flow - Hongjun Zhu; Huifen Xu; Bin Liu; Jiawen Zhong (Ocean Engineering, 2024)

Flotation-assisted electrodeposition process to recover copper from waste printed circuit boards - Yamin Li; Xuehao Wei; Hongjun Liu; Yan Sun (Chemical Engineering Journal, 2024)

Insights into in situ surface reconstruction in cobalt perovskite oxides for enhanced catalytic activity - Yanyu Jin; Hongjun Cheng; Qibao Wang; Xiaoqing Liu; Shengpeng Mo; Bin Zhou; Yue Peng; Yu Wang; Wenzhe Si; Junhua Li (Journal of Hazardous Materials, 2024)

Exhaust and evaporative volatile organic compounds emissions from vehicles fueled with ethanol-blended-gasoline - Ruikang Li; Chongzhi Zhong; Yang Ning; Yan Liu; Pengfei Song; Ruiguang Xu; Hongjun Mao (Environmental Pollution, 2024)

Site database for national strong motion stations in mainland China - Kun Ji; Yefei Ren; Chuanbin Zhu; Yuting Zhang; Xinxin Yao; Daren Wang; Peng Zhang; Hongjun Si; Tadahiro Kishida; Ye Liu; Saman Yaghmaei-Sabegh; Ruizhi Wen (Engineering Geology, 2024)

Research advances in the function and anti-aging effects of nicotinamide mononucleotide - Min Wang; Yuan Cao; Yun Li; Lu Wang; Yuyan Liu; Zihui Deng; Lianrong Zhu; Hongjun Kang (Journal of Zhejiang University-SCIENCE B, 2024)
Aging and age-related ailments have emerged as critical challenges and great burdens within the global contemporary society. Addressing these concerns is an imperative task, with the aims of postponing the aging process and finding effective treatments for age-related degenerative diseases. Recent investigations have highlighted the significant roles of nicotinamide adenine dinucleotide (NAD + ) in the realm of anti-aging. It has been empirically evidenced that supplementation with nicotinamide mononucleotide (NMN) can elevate NAD + levels in the body, thereby ameliorating certain age-related degenerative diseases. The principal anti-aging mechanisms of NMN essentially lie in its impact on cellular energy metabolism, inhibition of cell apoptosis, modulation of immune function, and preservation of genomic stability, which collectively contribute to the deferral of the aging process. This paper critically reviews and evaluates existing research on the anti-aging mechanisms of NMN, elucidates the inherent limitations of current research, and proposes novel avenues for anti-aging investigations.

TC activity affected the northern sea of the Shandong Peninsula over the past 1500 years and its driving mechanism - Wenzhe Lyu; Tengfei Fu; Zhen Cui; Yancheng Wang; Wenquan Liu; Xingyong Xu; Hongjun Yu (Marine Geology, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

New insights into the dominance of mixed fermentation of Staphylococcus cohnii and Staphylococcus saprophyticus in Chinese bacon: Complete genomic and comparative genomic perspectives - Li Yang; Hongjun Li; Han Wu; Xuelian Sun; Shuyun Liu; Dong Zhang; Chang Su; Zhifei He (Food Research International, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

A contagious disease caused serious damage to Gracilariopsis lemaneiformis cultivation in China - Tong Pang; Feng Wang; Xiaobin Yang; Jianguo Liu; Hongjun Xu; Qunqun Guo; Liyuan Liu (Journal of Applied Phycology, 2024)

Harnessing key bacteria from suppressive soil to mitigate banana Panama disease - Nana Lv; Mohammadhossein Ravanbakhsh; Shuqin Ling; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Zongzhuan Shen; Qirong Shen (Biology and Fertility of Soils, 2024)

Corrigendum to “Rice-fish coculture without phosphorus addition improves paddy soil nitrogen availability by shaping ammonia-oxidizing archaea and bacteria in subtropical regions of South China” [Sci. Total Environ. 927 (2024): 171642] - Xing Liu; Daolin Su; Huaqiao Huan; Jiaen Zhang; Hongjun Zhen; Qi Jia; Min Zhao (Science of The Total Environment, 2024)

Sedimentary evolution of the East China Sea with implications for the relationship between the East Asian winter and summer monsoon over the past 6.3 ka - Wenzhe Lyu; Tengfei Fu; Guangquan Chen; Qiao Su; Wenquan Liu; Yancheng Wang; Zhen Cui; Hongjun Yu; Xingyong Xu (Journal of Asian Earth Sciences, 2024)

Rice-fish coculture without phosphorus addition improves paddy soil nitrogen availability by shaping ammonia-oxidizing archaea and bacteria in subtropical regions of South China - Xing Liu; Daolin Sun; Huaqiao Huang; Jiaen Zhang; Hongjun Zheng; Qi Jia; Min Zhao (Science of The Total Environment, 2024)

Progress and perspective on the topological spin textures in two-dimensional van der Waals magnets - Hongjun Xu; Yizhou Liu; Giovanni Finocchio; Kang L. Wang; Guoqiang Yu (Science Bulletin, 2024)

Contrasting benthic bacterial and fungal communities in two temperate coastal areas affected by different levels of anthropogenic pressure - Zhen Wang; Xiaohan Liu; Xiaocheng Wang; Haining Wang; Yi Sun; Jinyong Zhang; Hongjun Li (Marine Environmental Research, 2024)

Effect of staphylococci fermentation and their synergistic Lactobacillus on the physicochemical characteristics and nonvolatile metabolites of Chinese bacon - Li Yang; Hongjun Li; Han Wu; Shuyun Liu; Zhifei He (Meat Science, 2024)

Optimizing humic acid breakdown and methane production via semiconductor-assisted photo-anaerobic digestion - Qiang Liu; Haoyu Zhang; Shuo Chen; Yeqing Li; Mahmoud Mazarji; Lu Feng; Junting Pan; Hongjun Zhou; Chunming Xu (Chemical Engineering Journal, 2024)

Microsatellite Analysis of the Influence of Sebastes schlegelii Restocking on the Genetic Structure of Stocks in Rongcheng Bay - Yi Zhang; Lijuan Wang; Zhihao Wu; Hongjun Liu; Zongcheng Song; Feng You (Thalassas: An International Journal of Marine Sciences, 2024)

Enhancing mechanism of extrusion pretreatment on bioconversion of distiller’s grains into microbial protein feed - Chenjie Wang; Yao Liu; Ruoyun Yuan; Ling Xu; Chunhui Xin; Yang Tang; Chengye Ma; Shanfeng Chen; Hongjun Li (Animal Feed Science and Technology, 2024)

Spatiotemporal dynamics of bacterioplankton communities in the estuaries of two differently contaminated coastal areas: Composition, driving factors and ecological process - Weiyue Zhang; Jinqing Ye; Xiaohan Liu; Yunlei Zhang; Jinyong Zhang; Lingyu Shen; Yuan Jin; Jianheng Zhang; Hongjun Li (Marine Pollution Bulletin, 2024)

Electricity-carbon coupling retail package optimization considering low-carbon benefits of distributed renewable energy - Hongjun Gao; Qianzhen Chen; Shuaijia He; Zhiyuan Tang; Haibo Li; Junyong Liu (Journal of Cleaner Production, 2024)

Seedless hydrothermal growth of piezoelectric photocatalytic ZnO nanowires on laser-ablated copper mesh for oil/water separation - Xiaohan Xing; Rui Zhou; Huangping Yan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2024)

Emerging disinfection byproducts 3-bromine carbazole induces cardiac developmental toxicity via aryl hydrocarbon receptor activation in zebrafish larvae - Yingying Liu; Xudong Jin; Yanan Ye; Zeqiong Xu; Zhongkun Du; Huachang Hong; Haiying Yu; Hongjun Lin; Xianfeng Huang; Hongjie Sun (Environmental Pollution, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Taxonomic and functional dynamics of nirS denitrifiers along a salinity gradient in the Pearl River Estuary - Hongwei Zhou; Hao Zhang; Xinping He; Cheng Liu; Fozia; Qian Cui; Hongjun Yang; Chunyu Zhao; Han Zhang; Huanhuan Hu; Zongxiao Zhang (Frontiers in Marine Science, 2024)
Understanding the factors that shape the diversity, distribution, and function of denitrifying microbes is vital for managing nitrogen cycling in these ecosystems. This study explores the diversity, biogeographic distribution, assembly processes, interaction, and denitrification potential of the nirS -encoding microbial community ( nirS denitrifier) in the Pearl River Estuary based on high-throughput and metagenomics sequencing dataset. The results of this study show that salinity is a crucial regulatory environmental factor that determines the spatial distribution, phylogenetic turnover, and co-occurrence patterns of nirS denitrifiers. Additionally, the dissolved organic carbon (DOC), suspended sediment concentration (SSC), and dissolved oxygen (DO) in water also significantly impact the biodiversity and abundance of nirS denitrifiers. Furthermore, our findings demonstrate that, in comparison to environmental factors, the ecological and evolutionary characteristics of nirS denitrifiers play a more prominent role in regulating their denitrification potential, suggesting that alterations in the microbial community within dynamic changes in estuarine water can profoundly affect its denitrification function. Our results indicate the significant roles of denitrification microbial structure and phylogenetic characteristics in maintaining their ecological functions. Future studies should continue to explore the interactions between microbial communities and environmental factors to further elucidate the denitrification process in estuaries and its implications for ecosystem health and water quality.

Spatial differences, distribution dynamics and driving factors of the synergy between marine ecological security and high-quality development in three major marine economic circles of China - Ran Ni; Hongjun Guan; Yichuan Wang; Yilin Liu (Frontiers in Marine Science, 2024)
Introduction In China, the sustainable development of the marine is facing a prominent contradiction between ecological security and economic development, as well as unbalanced and non-coordinated regional development. Exploring the regional differences in the synergy between marine ecological security (MES) and high-quality development of the marine economy (MHQD) and its driving mechanism is the key to optimizing the spatial distribution of marine development, promoting the synergistic and balanced development of the regional marine composite system during the “14th Five-Year Plan” period. Methods In this article, we employed the Dagum Gini coefficient decomposition model and Kernel density estimation methods to reveal the evolution of regional differences, sources, and distributional dynamics of synergistic development of the composite system from 2009 to 2020. Meanwhile, spatial econometric analyses were applied to identify the influencing factors and spatial spillover effects. Results The level of synergistic development of composite system has a fluctuating upward trend, with a significant positive spatial correlation and a significant “polarization effect”. Inter-regional differences in the synergistic development of the composite system are the main source of the overall differences. Factors such as innovation-driven, human capital, and opening up to the outside world are important driving factors for the synergistic development of the composite system. Discussion The MES-MHQD composite system exhibits a low level of synergistic development, with significant differences in the level of synergy both among the 3MMECs and within each circle. We infer that the expansion trend of overall difference will constrain the exploration of a sustainable development path for China’s coastal regions in the future. It is necessary to optimize the spatial layout of the composite system, establish robust mechanisms for regional cooperation and communication, accurately identify the development bottlenecks of the regional composite systems. This study provides a theoretical basis and decision-making reference for the promotion of the synergistic development of the composite system of the Three Major Marine Economic Circles (3MMECs) in China.

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Investigating the impact of high-altitude on vehicle carbon emissions: A comprehensive on-road driving study - Zhiwen Jiang; Lin Wu; Haomiao Niu; Zhenyu Jia; Zhaoyu Qi; Yan Liu; Qijun Zhang; Ting Wang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2024)

An integrated system combining Tetrasphaera-dominated enhanced biological phosphorus removal with sulfur autotrophic denitrification to enhance biological nutrients removal - Hongjun Liu; Wei Zeng; Qingan Meng; Jiayu Zhang; Yongzhen Peng (Science of The Total Environment, 2024)

The change of coordination environments induced by vacancy defects in hematite leads to a contrasting difference between cation Pb(II) and oxyanion As(V) immobilization - Yongjin Xiang; Juan Liu; Yiwen Chen; Hongjun Zhang; Lu Ren; Bangjiao Ye; Wenfeng Tan; Kappler Andreas; Jingtao Hou (Environmental Pollution, 2024)

Research on the impact mechanism of scientific and technological innovation on the high-quality development of the marine economy - Min Feng; Hongjun Guan; Yichuan Wang; Yilin Liu (Frontiers in Marine Science, 2024)
Promoting the high-quality development of the marine economy is an inevitable choice for building a maritime power, and technological innovation can provide strong impetus for the high-quality development of the marine economy. Therefore, it is urgent to clarify the impact mechanism of technological innovation on the high-quality development of the marine economy, and promote the high-quality development of the marine economy. This study employs panel data from 11 coastal provinces and municipalities (autonomous regions) in China, spanning the years 2006 to 2020. The objective is to empirically evaluate the mechanism through which scientific and technical innovation impacts the high-quality development of the marine economy. This is achieved by utilizing the PVAR model and the mediation effect model. The research findings indicate that there is a noteworthy impact of enhancing scientific and technological innovation on the marine economy of China. Moreover, there exists a significant reciprocal relationship between scientific and technological innovation and the pursuit of high-quality development in the marine economy. It is observed that scientific and technological innovation not only has a positive influence on the high-quality development of the marine economy by enhancing green total factor productivity and optimizing the industrial structure, but it also facilitates the advancement of the marine economy through the chain mediation path of “improving green total factor productivity and optimizing industrial structure”.

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Valorization of chitin derived N-acetyl-D-glucosamine into N-containing chemical 3-acetamido-5-acetylfuran by a facile, efficient and low cost composite additive - Hongjun Zang; Zhipeng Liu; Changchun Wu; Yulong Chang; Xiangling Zhu; Xi Zhu; Meng Yan (Sustainable Chemistry and Pharmacy, 2024)

Experimental study of structure dimensions effects on local scour of submerged compound suction anchor foundation - Chenghao Zhu; Wenyu Wu; Xiaoli Liu; Hongjun Liu; Ruigeng Hu; Peng Yu (Ocean Engineering, 2024)

Experimental and numerical investigation on the impact of MS2AF on local scour protection performance - Chenghao Zhu; Qiheng Li; Jianguo Zheng; Hongjun Liu; Peng Yu (Ocean Engineering, 2024)

Optimizing sludge retention time for sustainable photo-enhanced biological phosphorus removal systems: Insights into nutrient fate, microbial community, and bacterial phototolerance - Qingan Meng; Wei Zeng; Hongjun Liu; Jiayu Zhang; Biao Ma; Yongzhen Peng (Journal of Environmental Management, 2024)

Staphylococcus inoculation enhances the sensorial attributes of Chinese bacon by coordinating the composition of flavor compounds through amino acid metabolism - Li Yang; Hongjun Li; Han Wu; Shunyun Liu; Zhifei He (Food Research International, 2024)

Multi-spherical interactions and mechanisms of hydrocarbon enrichment in the Southeast Asian archipelagic tectonic system - Rixiang Zhu; Hongjun Wang; Huajian Wang; Xiaomei Wang; Bo Wan; Wang Zhang; Houqin Zhu; Yuke Liu; Junlai Liu; Qinren Meng; Fang Hao; Zhijun Jin (Science China Earth Sciences, 2024)

Phosphorylation of RGS16 at Tyr168 promote HBeAg-mediated macrophage activation by ERK pathway to accelerate liver injury - Miaomiao Tian; Nijin Wu; Xiaoyu Xie; Tiantian Liu; Yajing You; Shujun Ma; Hongjun Bian; Huiling Cao; Le Wang; Chenxi Liu; Jianni Qi (Journal of Molecular Medicine, 2024)

Multiscale evaluation of the structural characteristics of intact loess subjected to wet/dry cycles - Kuan Liu; Wanjun Ye; Hongjun Jing (Natural Hazards, 2024)

Dynamical graph neural network with attention mechanism for epilepsy detection using single channel EEG - Yang Li; Yang Yang; Qinghe Zheng; Yunxia Liu; Hongjun Wang; Shangling Song; Penghui Zhao (Medical & Biological Engineering & Computing, 2024)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Zero-carbon-driven multi-energy coordinated sharing model for building cluster - Hongjun Gao; Leilei Wang; Shuaijia He; Junyong Liu (Journal of Cleaner Production, 2023)

Dynamic characteristics of net anthropogenic phosphorus input to the upper Yangtze River Basin from 1989 to 2019: Focus on the phosphate ore rich area in China - Junlan Yang; Min Li; Lu Liu; Hongjun Zhao; Wenqing Luo; Yali Guo; Xiaonan Ji; Wei Hu (Journal of Environmental Management, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Assembly and phylogenetic analysis of the mitochondrial genome of endangered medicinal plant Huperzia crispata - Yu Cao; Dengpan Yin; Bo Pang; Haibo Li; Qiao Liu; Yufeng Zhai; Nan Ma; Hongjun Shen; Qiaojun Jia; Dekai Wang (Functional & Integrative Genomics, 2023)

The successful application of light to the system of simultaneous nitrification/endogenous denitrification and phosphorus removal: Promotion of partial nitrification and glycogen accumulation metabolism - Qingan Meng; Wei Zeng; Hongjun Liu; Mengjia Zhan; Jiayu Zhang; Hongan Wu (Water Research, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

AnWRKY29 from the desert xerophytic evergreen Ammopiptanthus nanus improves drought tolerance through osmoregulation in transgenic plants - Shuyao Wang; Yahui Liu; Xin Hao; Zhaoyuan Wang; Yingying Chen; Yue Qu; Hongjun Yao; Yingbai Shen (Plant Science, 2023)

Chemical characteristics of fine tire wear particles generated on a tire simulator - Quanyou Guo; Zhengyu Men; Zhenguo Liu; Zhihui Niu; Tiange Fang; Fengyang Liu; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Enhanced biological phosphorus removal systems adapting to seawater intrusion: Impacts of varying carbon source on metabolic adaptation in Candidatus Accumulibacter phosphatis - Qingan Meng; Wei Zeng; Mengjia Zhan; Hongjun Liu; Jiayu Zhang; Xianchun Lu; Yongzhen Peng (Chemical Engineering Journal, 2023)

N-doped carbon quantum dots enhance anaerobic digestion under light condition: The performances and potential mechanisms - Qiang Liu; Shuo Chen; Haoyu Zhang; Lu Feng; Hongjun Zhou; Junting Pan; Yeqing Li; Chunming Xu (Chemical Engineering Journal, 2023)

Denitrifying phosphorus removal (DPR) performance and metabolic mechanisms of Tetrasphaera at long-term nitrite exposure - Jiayu Zhang; Wei Zeng; Qingan Meng; Hongjun Liu; Sijia Lu; Yongzhen Peng (Chemical Engineering Journal, 2023)

Amplification-free microRNA profiling with femtomolar sensitivity on a plasmonic enhanced fluorescence nano-chip - Ruibin Hu; Yiyi Liu; Guanghui Wang; Jiahui Lv; Jingkai Yang; Hongjun Xiao; Ying Liu; Bo Zhang (Analytica Chimica Acta, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

Configuration modulation of vermiculite by exfoliation coupled Cu(II) anchoring for boosting removal of tetracycline via synergy of adsorption and photocatalysis - Ping Zhang; Mingxue Xiang; Wei Jiang; Huiling Liu; Yu Chen; Ying Fang; Longyong Wu; Hongjun Guo; Yufei Wang (Chemical Engineering Journal, 2023)

Seasonal implications for taxonomic sufficiency to simplify M-AMBI methodology in the coastal area adjacent to a eutrophic estuary - Chenman Yang; Hongjun Song; Yi Sun; Pengfei Xie; Yuan Liu; Hongjun Li (Acta Oceanologica Sinica, 2023)

Moderately delayed maturation of composting promotes the reduction of guild-plant pathogenic fungi within vegetable waste - Zijian Lv; Chengyuan Tao; Jiawei Zhang; Zongzhuan Shen; Dongsheng Wang; Bei Wang; Hongjun Liu; Rong Li (Environmental Science and Pollution Research, 2023)

Carbon quantum dots in-situ relieve humic acids inhibition on methanogens while significantly increasing the abundance of Methanosarcinaceae - Qiang Liu; Yuanting Xu; Yeqing Li; Chengjie Ma; Shuo Chen; Lu Feng; Quan Xu; Junting Pan; Bo Peng; Hongjun Zhou; Chunming Xu (Journal of Cleaner Production, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Green electricity trading driven low-carbon sharing for interconnected microgrids - Hongjun Gao; Mingyang Hu; Shuaijia He; Junyong Liu (Journal of Cleaner Production, 2023)

Phenol degradation at high salinity by a resuscitated strain Pseudomonas sp. SAS26: kinetics and pathway - Shusheng Zhang; Zijing An; Xiaomei Su; Aiqin Hou; Leilei Liu; Lihua Zhang; Qiuyang He; Faqian Sun; Zupei Lei; Hongjun Lin; Jiahou Lai (Journal of Environmental Chemical Engineering, 2023)

Identification of monoclonal antibody targeting epitope on p72 trimeric spike of African swine fever virus - Xulai Duan; Yingnan Liu; Zongyan Chen; Zhenhua Xie; Chuanwen Tian; Yao Li; Lu Lv; Rongrong Wang; Jingyi Liu; Hongjun Chen (Virus Genes, 2023)

Bibliometric analysis and mini-review of global research on pyroptosis in the field of cancer - Wenwen Wang; Wenhuizi Sun; Han Xu; Yao Liu; Chenlu Wei; Siqiao Wang; Shuyuan Xian; Penghui Yan; Jiajun Zhang; Hongjun Guo; Hengwei Qin; Jie Lian; et al. (Apoptosis, 2023)

Softening/Hardening Damage Model and Numerical Implementation of Seabed Silt-Steel Interface in Yellow River Underwater Delta - Peng Yu; Honghua Liu; Lin Geng; Shuai Wang; Yang Yu; Chenghao Zhu; Qi Yang; Hongjun Liu; Yong Guan (Journal of Marine Science and Engineering, 2023)
The interaction between soil and structure is a research hotspot in ocean engineering, and the shear performance of interfaces is an essential factor affecting the bearing capacity of offshore structures. Taking the Yellow River Underwater Delta as the research area, the Softening/Hardening damage model of the silt–steel interface and the determination method of model parameters are proposed based on the statistical damage theory. Through the interface monotonic shear test under the conditions of different normal stress, roughness and water content, the shear mechanical properties and volumetric deformation laws on the silt–steel interface are analyzed, and the damage model parameters are obtained. Finally, a FRIC subroutine for the damage model was developed based on ABAQUS. The research results indicate the following: (1) The interface between silt and steel exhibits two characteristics, softening/hardening and shear shrinkage/expansion, under different conditions. Roughness significantly impacts interfacial cohesion, while water content mainly affects the internal friction angle. (2) The softening model based on the classic rock damage model can better simulate the stress–strain relationship of the silt–steel interface under high normal stress and low water content. In contrast, the hardening model based on the classic hyperbola model can better simulate the stress–strain relationship under low normal stress and high water content. The calculated results of the softening/hardening model agree with the experimental results, and the model has 7 parameters. (3) The developed FRIC subroutine can effectively simulate the nonlinear mechanical behavior of the interface between silt and steel. The research results provide a reference for exploring the stability analysis of offshore structures considering interface weakening effects.

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liangfeng Liu; Jianqing Tian; Hongjun Wang; Dan Xue; Xinya Huang; Ning Wu; Meng Wang; Xingliang Xu; Changhui Peng; Yanfen Wang; Huai Chen (Soil Biology and Biochemistry, 2023)

Investigation on dynamic performance of wind turbines using different scaling methods in wind tunnel tests - Kun Lin; Shaohui Xiao; Hongjun Liu; Annan Zhou (Engineering Structures, 2023)

Characterization and phylogenetic analysis of bovine gammaherpesvirus 4 isolated in China, 2022 - Weiqiang Guo; Tong Sun; Yingnan Liu; Xulai Duan; Chuanwen Tian; Zhou Zhou; Yong-Sam Jung; Jingyi Liu; Hongjun Chen (Virus Genes, 2023)

An Innovative Approach to Predicting Scour Depth Around Foundations Under Combined Waves and Currents in Large-Scale Tests Based on Small-Scale Tests - Ruigeng Hu; Hongjun Liu; Yao Lu; Xiuhai Wang; Wei Shi (Journal of Ocean University of China, 2023)

Deformation analysis of underwater shield tunnelling based on HSS model parameter obtained by the Bayesian approach - Yao Lu; Peng Yu; Yan Zhang; Jian Chen; Tao Liu; Han Wang; Hongjun Liu (Frontiers in Marine Science, 2023)
Deformation analysis and control of underwater large-diameter shield tunnels is a prerequisite for safe tunnel construction. Reasonable selection of constitutive model and its parameters is the key to accurately predicting the deformation induced by underwater shield tunnelling. In this paper, the finite element analysis of cavity expansion during the piezocone penetration test (CPTU) based on the hardening soil model with small strain stiffness (HSS) model was carried out, and the correlation model of the normalized cone tip resistance Q with the reference secant modulus E 50 ref and the effective internal friction angle φ ’ was established and verified using mini CPTU chamber test. Then, a Bayesian probability characterization approach for E 50 ref of silty clay based on CPTU was proposed. Furthermore, the deformation analysis of Jinan Yellow River tunnel crossing the south embankment was carried out to verify the reliability of the proposed approach. The good agreement between the field measurement and numerical simulation confirms that the parameters obtained by the Bayesian approach are reliable. Finally, a sensitivity analysis was performed to study the law of riverbed settlement induced by underwater large-diameter shield tunnelling. The results show that the increasing support pressure could effectively reduce the riverbed settlement, but there is an upper limit. The optimal support pressure of established model is between 0.45 MPa and 0.5 MPa. The uphill section causes greater riverbed settlement than the downhill section. Under the same condition, increasing buried depth and water level will lead to a more significant settlement.

Modification mechanism of protein in rice adjuncts upon extrusion and its effects on nitrogen conversion during mashing - Lijun Jiang; Jialin Song; Mingming Qi; Wenjing Suo; Yuxin Deng; Yao Liu; Luxia Li; Dongliang Zhang; Chenjie Wang; Hongjun Li (Food Chemistry, 2023)

Interactions Between Humic Acid and the Forms and Bioavailability of Copper in Water - Hongwei Pan; Lili Shi; Xin Liu; Hongjun Lei; Guang Yang; Huiru Chen (Water, Air, & Soil Pollution, 2023)

Distinct ecological mechanisms drive the spatial scaling of abundant and rare microbial taxa in a coastal sediment - Xia Liu; Hongjun Li; Wen Song; Qichao Tu (Journal of Biogeography, 2023)
Aim Revealing the ecological mechanisms driving the diversity patterns of microbial communities across space and through time is an essential issue in microbial biogeography. This study links microbial spatial scaling with ecological mechanisms, aiming to provide novel mechanistic insights into the biogeographic patterns followed by different types of microbes. Location Beibu Gulf, a semi‐enclosed oceanic bay located on the southern coast of China. Taxon Bacteria, which were further classified as abundant and rare taxa. Methods By employing high throughput sequencing, two typical spatial scaling models, diversity‐area (DAR) and distance‐decay relationships (DDR), were investigated for the abundant and rare microbial communities in a coastal sediment ecosystem. Both alpha‐ and beta‐diversity indices were extended to Hill numbers to verify the contribution of abundant and rare taxa to DAR and DDR. The iCAMP approach was used to quantify the contribution of different ecological processes in structuring microbial communities. Results Strong spatial scaling patterns were observed for the whole communities and the rare subcommunities but only weak patterns for the abundant subcommunities. Rare subcommunities were mainly responsible for the observed spatial scaling patterns, as confirmed by extending spatial scaling diversity metrics to Hill numbers. Both environmental heterogeneity and local community assembly mechanisms drove the spatial scaling of microbial communities. Strong ecological drift and dispersal limitation underlay the spatial scaling of rare subcommunities, whereas high homogeneous selection weakened the spatial scaling of abundant subcommunities. Main Conclusions Rare taxa were mainly responsible for the biogeographic patterns followed by sediment microbial communities in the Beibu Gulf. Distinct ecological mechanisms underlay the different biogeographic patterns followed by abundant and rare subcommunities.

SIRT3/GLUT4 signaling activation by metformin protect against cisplatin-induced ototoxicity in vitro - Peiyu Du; Tianyi Liu; Pan Luo; Hejie Li; Wei Tang; Shimin Zong; Hongjun Xiao (Archives of Toxicology, 2023)

Facile construction of Z-scheme AgCl/Bi3TaO7 photocatalysts for effective removal of tetracycline under visible-light irradiation - Xiaoxin Guo; Jun Liu; Dan Li; Hongjun Cheng; Kankan Liu; Xiaoqing Liu; Tiansheng Liu (Environmental Science and Pollution Research, 2023)

Hydrochemical characteristics and quality assessment of groundwater in Guangxi coastal areas, China - Tengfei Fu; Chenzhe Li; Zhenyan Wang; Chen Qi; Guangquan Chen; Yushan Fu; Qiao Su; Xingyong Xu; Wenquan Liu; Hongjun Yu (Marine Pollution Bulletin, 2023)

Inhibitory effect and mechanism of a compound essential oils on Cladophora glomerata - Yanqun Wang; Dengyu Wang; Wenxi Zhao; Hongjun Liu; Li Li; Jie Bai (Marine Pollution Bulletin, 2023)

Research on 90-day subchronic toxicities of the ethanol extract from the cultivated Fritillaria Cirrhosa bulbs by oral administration in Sprague-Dawley rats - Xiao Liu; Tse Wai Ming; Tse Kathy Wai Gaun; Hai Xiong; A.G.A. Er-bu; Hongjun Xie; Gonggalanzi; Yun Xu; Bengui Ye (Regulatory Toxicology and Pharmacology, 2023)

Mechanism analysis and experimental verification of the bulging vibration characteristic of a fluid-solid metamaterial - Zichun Yi; Zhiwei Zhang; Jiankun Huang; Hongjun Xiang; Caisong He; Lanhua Liu (Engineering Structures, 2023)

Impacts of heatwaves and cold spells on glaucoma in rural China: a national cross-sectional study - Ai Zhang; Qihua Wang; Xueli Yang; Yuanyuan Liu; Jiayu He; Anqi Shan; Naixiu Sun; Qianfeng Liu; Baoqun Yao; Fengchao Liang; Ze Yang; Xiaochang Yan; et al. (Environmental Science and Pollution Research, 2023)
China faces increasing health risks from climate change. The structure and function of the eye and vision were affected by extreme heat and cold. The study aimed to evaluate the impacts of heatwaves and cold spells on glaucoma. A national cross-sectional study of the Rural Epidemiology for Glaucoma (REG-China) was conducted in ten provinces of China, and 36,081 adults aged 40 years or more were included. Glaucoma signs were assessed via a standard examination. A total of 15 heatwave definitions, based on intensity (95th to 99th percentiles of temperature distribution) and duration (≥2 days, 3 days, and 4 days), were used to quantify heatwave effects, and 6 cold spell definitions were defined based on threshold temperature percentile (5th and 10th) and duration (3 days, 5 days, and 9 days). Multivariable-adjusted logistic regression models paired with interaction analysis were performed to investigate the impacts of heatwaves and cold spells on glaucoma, and the dose-response relationships were assessed using a restricted cubic spline (RCS) model. Subgroup analysis was conducted stratified by gender, age, smoking status, occupation, and family history of glaucoma. The overall prevalence of glaucoma was 2.1% (95% CI 1.94–2.25%). Higher heatwaves were significantly correlated with higher OR of glaucoma, with the OR (95% CI) ranging from 1.014 (1.009, 1.018) to 1.090 (1.065, 1.115) by different definitions. Glaucoma was affected by heatwaves more strongly than by cold spells. The effects of both heatwaves and cold spells were higher in males than females and in smokers than nonsmokers. These results of the present study evoked the attention of prospective research to elucidate the relationship between extreme temperatures and eye diseases.

Spatiotemporal variation of cultivated land ecosystem stability in typical regions of Lower Liaohe Plain China based on stress - buffer - response - Hongjun Sui; Ge Song; Wanying Liu; Yuxin Zhang; Ruiqing Su; Quanxi Wang; Gaofeng Ren; Yuqi Mi (Science of The Total Environment, 2023)

Study of spatialtemporal changes in Chinese forest eco-space and optimization strategies for enhancing carbon sequestration capacity through ecological spatial network theory - Shi Qiu; Minzhe Fang; Qiang Yu; Teng Niu; Hongjun Liu; Fei Wang; Chenglong Xu; Mingsi Ai; Jieyu Zhang (Science of The Total Environment, 2023)

A novel process for simultaneous biological nutrient removal and waste activated sludge reduction in one-stage system without aeration - Zhiwei Fan; Wei Zeng; Yuan Jia; Qingan Meng; Hongjun Liu; Hong Liu; Yongzhen Peng (Chemical Engineering Journal, 2023)

CircRNA3616 knockdown attenuates inflammation and apoptosis in spinal cord injury by inhibiting TLR4/NF-κB activity via sponging miR-137 - Li Wang; Zhiwen Song; Hongjun Zou; Haining Chen; Yong Hu; Xiangnan Li; Jinbo Liu (Molecular and Cellular Biochemistry, 2023)

Experimental Investigation on the Cyclic Shear Mechanical Characteristics and Dynamic Response of a Steel–Silt Interface in the Yellow River Delta - Peng Yu; Jie Dong; Yong Guan; Qing Wang; Shixiang Jia; Meijun Xu; Hongjun Liu; Qi Yang (Journal of Marine Science and Engineering, 2023)
The shear behavior and dynamic response of a steel–silt interface are significant for the safety and stability of offshore structures in the Yellow River Delta. A series of steel–silt interface cyclic shear tests under constant normal load conditions (CNL) were carried out to explore the effects of normal stress, shear amplitude, roughness, and water content on the interface shear strength, shear stiffness, and damping ratio using a large interface shear apparatus. The preliminary results showed that the amplitude of normal stress and shear amplitude affected the interface’s shear strength, stiffness, and damping ratio in a dominant manner. The roughness and water content were also crucial factors impacting the rule of shear strength, shear stiffness, and damping ratio, changing with the number of cycles. Under various scenarios, the steel–silt interface weakened distinctively, and the energy dissipation tended to be asymptotic with the cyclic shear.

Emissions of air pollutants from non-road construction machinery in Beijing from 2015 to 2019 - Xueyao Li; Liu Yang; Yongteng Liu; Chongbo Zhang; Xiaohong Xu; Hongjun Mao; Taosheng Jin (Environmental Pollution, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

A data-driven approach for the measurement and improvement of regional industrial ecological efficiency for carbon peaking and carbon neutralization - Fan Liu; Cuixia Zhang; Yingyan Zhang; Hongjun Liu (Environmental Science and Pollution Research, 2023)

Life Cycle Greenhouse Gas Emission Assessment for Using Alternative Marine Fuels: A Very Large Crude Carrier (VLCC) Case Study - Jinjin Huang; Hongjun Fan; Xiangyang Xu; Zheyu Liu (Journal of Marine Science and Engineering, 2022)
The International Maritime Organization (IMO) has set decarbonisation goals for the shipping industry. As a result, shipowners and operators are preparing to use low- or zero-carbon alternative fuels. The greenhouse gas (GHG) emission performances are fundamental for choosing suitable marine fuels. However, the current regulations adopt tank-to-wake (TTW) emission assessment methods that could misrepresent the total climate impacts of fuels. To better understand the well-to-wake (WTW) GHG emission performances, this work applied the life cycle assessment (LCA) method to a very large crude carrier (VLCC) sailing between the Middle East and China to investigate the emissions. The life cycle GHG emission impacts of using alternative fuels, including liquified natural gas (LNG), methanol, and ammonia, were evaluated and compared with using marine gas oil (MGO). The bunkering site of the VLCC was in Zhoushan port, China. The MGO and LNG were imported from overseas, while methanol and ammonia were produced in China. Four production pathways for methanol and three production pathways for ammonia were examined. The results showed that, compared with MGO, using fossil energy-based methanol and ammonia has no positive effect in terms of annual WTW GHG emissions. The emission reduction effects of fuels ranking from highest to lowest were full solar and battery-based methanol, full solar and battery-based ammonia, and LNG. Because marine ammonia-fuelled engines have not been commercialised, laboratory data were used to evaluate the nitrous oxide (N2O) emissions. The GHG emission reduction potential of ammonia can be exploited more effectively if the N2O emitted from engines is captured and disposed of through after-treatment technologies. This paper discussed three scenarios of N2O emission abatement ratios of 30%, 50%, and 90%. The resulting emission reduction effects showed that using full solar and battery-based ammonia with 90% N2O abatement performs better than using full solar and battery-based methanol. The main innovation of this work is realising the LCA GHG emission assessment for a deep-sea ship.

The complete chloroplast genome of the medical plant Huperzia crispata from the Huperziaceae family: structure, comparative analysis, and phylogenetic relationships - Dengpan Yin; Bo Pang; Haibo Li; Qiao Liu; Yufeng Zhai; Nan Ma; Tongtong Chen; Hongjun Shen; Qiaojun Jia; Dekai Wang (Molecular Biology Reports, 2022)

Analysis of Cyclic Shear Stress–Displacement Mechanical Properties of Silt–Steel Interface in the Yellow River Delta - Peng Yu; Jie Dong; Haisong Liu; Rui Xu; Rujie Wang; Meijun Xu; Hongjun Liu (Journal of Marine Science and Engineering, 2022)
Pile foundations of offshore structures are often subjected to cyclic loads under storm loads, thus reducing their vertical bearing capacity. Therefore, studying the cyclic shear behavior of the soil–structure interface is important for maintaining the stability of offshore structures. A series of cyclic shear tests of the silt–steel interface were carried out using a large interface shear apparatus. The effects of various factors (i.e., normal stress, shear displacement amplitude, roughness, and water content) on the shear stress characteristics of the silt–steel interface were investigated. The stress–displacement model of the cyclic shear silt–steel interface was deduced. The results showed that the shear stress at the silt–steel interface was softened, and the type of bulk deformation was shear shrinkage under cyclic shear. With the increase in shear amplitude, the hysteresis curve gradually developed from “parallelogram” to “shuttle” and “hysteresis cake”. With the increase in normal stress and roughness and the decrease in water content, the interfacial shear strength, volume displacements growth rate, and growth rate increased. The stress–displacement mathematical model of the silt–steel interface based on the modified hyperbolic model was in good agreement with the test data.

PseAraUbi: predicting arabidopsis ubiquitination sites by incorporating the physico-chemical and structural features - Wei Wang; Yu Zhang; Dong Liu; HongJun Zhang; XianFang Wang; Yun Zhou (Plant Molecular Biology, 2022)

Two-stage hybrid network for segmentation of COVID-19 pneumonia lesions in CT images: a multicenter study - Yaxin Shang; Zechen Wei; Hui Hui; Xiaohu Li; Liang Li; Yongqiang Yu; Ligong Lu; Li Li; Hongjun Li; Qi Yang; Meiyun Wang; Meixiao Zhan; et al. (Medical & Biological Engineering & Computing, 2022)

Response of soil carbon fractions and enzyme activities to mowing management on in a coastal wetland of the yellow river delta - Qian Cui; Hongjun Yang; Guangmei Wang; Jinzhao Ma; Lu Feng; Jingtao Liu (Frontiers in Marine Science, 2022)
Coastal wetlands are considered as important “blue carbon” sink, and mowing management induced by anthropogenic activities is anticipated to profoundly affect soil carbon stocks in coastal wetlands. However, the impacts of mowing management on soil organic carbon (SOC) and enzyme activities and the mechanisms responsible for associated changes in Phragmites australis wetland remain uncertain. We conducted a field mowing manipulation experiment [control (CK), mowing and returning straw in December (12MS), mowing and removing straw in December (12MR), mowing and returning straw in March (3MS), and mowing and removing straw in March (3MR)] in P. australis wetland of the Yellow River Delta and quantified their impacts on soil quality, SOC, SOC fractions, and enzyme activities. Results showed that mowing treatments led to overall increases in soil nutrients [total carbon (TC), total nitrogen (TN), total phosphorus (TP), NH 4 + , and NO 3 − ] and decreases in soil C/N ratio. The effects of mowing treatments on soil nutrient content were pronounced on topsoil than deep soil, and the maximum value of TC, TN, and TP reached in the 12MR treatment. Compared with CK, the 12MS, 12MR, 3MS, and 3MR treatments at 0–10 cm depth significantly enhanced SOC content by 8.78%, 32.9%, 16.5%, and 30.1%, respectively, but only the 3MS treatment enhanced SOC by 16.5% at 10–20 cm depth. Mowing treatments increased dissolved organic carbon (DOC), microbial biomass carbon (MBC), particulate organic carbon (POC), and labile organic carbon (LOC) and the contents of DOC, MBC, POC, and LOC decreased with soil depth. Mowing treatments stimulated the activities of sucrase and urease in topsoil, but only the 3MR treatment improved alkaline phosphatase activity in topsoil. Path analysis indicated that mowing management dominantly modulates SOC by changing sucrase activity, alkaline phosphatase activity, TN, TP, NH 4 + , NO 3 − , DOC, and LOC in 0–10 cm depth. However, SOC was significantly controlled by sucrase activity, urease activity, TC, TN, TP, LOC, and POC in 10–20 cm depth. Collectively, our results indicate that the continuous mowing management is beneficial to enhance soil quality and carbon storage capacity of P. australis wetlands, which will contribute to enhance carbon sequestration and sink capacity of coastal wetlands.

Daytime warming triggers tree growth decline in the Northern Hemisphere - Wenjing Tao; Kangshan Mao; Jiang He; Nicholas G. Smith; Yuxin Qiao; Jing Guo; Hongjun Yang; Wenzhi Wang; Jianquan Liu; Lei Chen (Global Change Biology, 2022)
Global warming has been linked to declines in tree growth. However, it is unclear how the asymmetry in daytime and nighttime warming influences this response. Here, we use 2947 residual tree‐ring width chronologies covering 32 species at 2493 sites, between 1901 and 2018, across the Northern Hemisphere, to analyze the effects of daytime and nighttime temperatures, precipitation, and drought stress on the radial growth of trees. We show that drought stress was primarily triggered by daytime rather than nighttime warming. The radial growth of trees was more sensitive to drought stress in warm regions than in cold regions, especially for angiosperms. Our study provides robust evidence that daytime warming is the primary driver of the observed declines in forest productivity related to drought stress and that daytime and nighttime warming should be considered separately when modelling forest–climate interactions and feedbacks in a future, warmer world.

Genome characterization and comparative analysis among three swimming crab species - Ming Liu; Shanshan Ge; Shivish Bhandari; Chunlei Fan; Yu Jiao; Chunlei Gai; Youhong Wang; Hongjun Liu (Frontiers in Marine Science, 2022)
In this study we sequenced the genomes of three economically important swimming crabs Portunus trituberculatus, Charybdis japonica , and Callinectes sapidus using the next-generation sequencing approach and made a basic assembly. The genomes of the three species are characterized with high heterozygosity (>1.2%) and high repeat content (>50%). Genome comparative analysis revealed 40 long conserved fragments (>5,000 bp) among the three species, most of them are involved in cardiac-related biological process. Relative higher genome similarity was found between P. trituberculatus and C. japonica that are belong to different subfamilies, compared to that between P. trituberculatus and C. sapidus which are from the same subfamily. It is inconsistent with their phylogenetic evolutionary trees inferred from previous mitochondrial DNA coding fragments and a conserved ANK2 protein fragment from this study. We speculated that the high genome similarity between P. trituberculatus and C. japonica might be attributed to their same inhabit range in which the genome is subject to the same environment selection, and the inconsistence between genome similarity and phylogenetic relationship is caused by the different evolutionary rates of coding DNA and non-coding DNA under environment selection.

Numerical Study of Local Scour around Tripod Foundation in Random Waves - Ruigeng Hu; Xiuhai Wang; Hongjun Liu; Da Chen (Journal of Marine Science and Engineering, 2022)
In this study, the local scour around tripods in random waves is numerically investigated. The seabed-tripod-fluid numerical model with an RNG k−ε turbulence model is built and validated. Following that, the scour characteristics and flow velocity distribution are analyzed using the present numerical model. Finally, a revised stochastic model is proposed to predict the equilibrium scour depth, Seq, around tripods in random waves. The results indicate that the present seabed-tripod-fluid numerical model is capable of depicting the scour process and of capturing the flow field around tripods with high accuracy. Due to the blockage effects of the main column and structural elements, there is enhanced flow acceleration underneath the main column and the lower diagonal braces, which increases the turbulence intensity and seabed shear stress, causing more particles to be mobilized and transported, resulting in more severe scour at the site. The revised stochastic model shows the best agreement with the numerical and experimental results when n = 20, but more experimental data and numerical results are still needed to verify the adaptation of the revised stochastic model for larger Keulegan–Carpenter (KC) number conditions (KCrms,a > 4).

Scour Characteristics and Equilibrium Scour Depth Prediction around a Submarine Piggyback Pipeline - Ruigeng Hu; Xiuhai Wang; Hongjun Liu; Hao Leng; Yao Lu (Journal of Marine Science and Engineering, 2022)
Local scour around a submarine piggyback pipeline in combined waves and current is investigated experimentally. Based on the experimental results, the scour evolution and scour morphology are firstly analyzed. Then, a comparison with the equilibrium scour depth Seq between the present experimental data and predicted results is conducted. After that, the correlation between the dimensionless scour timescale T* and the maximum Shields parameter θcw is investigated, and a formula is obtained to describe the variation trend between T* and θcw for different gap ratios G/D. Furthermore, the parametric study is carried out to study the effects of Reynolds number Red and θcw on Seq, respectively. The results indicate that the Seq below the piggyback pipeline increases when the gap ratio G/D increases from 0 to 0.1, and it gradually decreases when G/D > 0.1. For a given KC, the Seq increases with the increase of the ratio of velocities Ucw. In addition, when Ucw is fixed, a higher KC results in a greater Seq. The T* is closely related to θcw and G/D. The higher Red and θcw both tend to result in the greater scour depth below a piggyback pipeline in combined waves and current.

Research on Corrosion Effect of Sulfate Ions on Concrete Under Wetting-Drying Cycle - Xiuhai Wang; Zhuangcai Tian; Yanan Zhang; Xiuting Su; Hongjun Liu; Tao Liu (Journal of Ocean University of China, 2022)

Scour Protection of Submarine Pipelines Using Ionic Soil Stabilizer Solidified Soil - Ruigeng Hu; Xiuhai Wang; Hongjun Liu; Hao Leng (Journal of Marine Science and Engineering, 2022)
A novel scour protection approach for pipeline using the Ionic Soil Stabilizer (ISS) solidified soil was proposed in this study. The ISS-solidified slurry can be poured adjacent to the pipeline immediately after it was placed, or in the growing scour holes. In the present study, the first type was utilized as the scour protection layer around the pipeline. A series of laboratory flume tests were conducted to validate the protective capacity of ISS-solidified slurry for the pipeline in waves and combined waves and current. Then, the scanning electron microscope (SEM) tests and pore size tests were carried out, respectively, to investigate the mechanism of ISS-solidified slurry for scour protection around the pipeline. Finally, the effects of the ISS-solidified layer for liquefaction stability of non-cohesive subsoil were evaluated. The results indicated that the ISS-solidified slurry is a reliable, economic approach for scour protection around pipelines in the ocean environment. It is noteworthy that if a non-cohesive soil layer underlies the ISS-solidified slurry, it is vulnerable to suffer accumulated liquefaction due to the dense crust structure of the ISS-solidified layer, so the adverse effects for accumulated liquefaction should be considered carefully due to the set of the ISS-solidified layer.

The addition of sawdust reduced the emission of nitrous oxide in pig manure composting by altering the bacterial community structure and functions - Chao Liu; Jiao Yan; Qian Huang; Hongjun Liu; Cece Qiao; Rong Li; Biao Shen; Qirong Shen (Environmental Science and Pollution Research, 2022)

Productivity calculating method in tight gas reservoirs considering the stress sensitivity - Jie He; Xiangdong Guo; Hongjun Cui; Kaiyu Lei; Yanyun Lei; Lin Zhou; Qinghai Liu; Yushuang Zhu; Linyu Liu (Arabian Journal of Geosciences, 2022)

Experimental Study of Local Scour around Tripod Foundation in Combined Collinear Waves-Current Conditions - Ruigeng Hu; Xiuhai Wang; Hongjun Liu; Yao Lu (Journal of Marine Science and Engineering, 2021)
A series of laboratory experiments were conducted in a wave-current flume to investigate the scour evolution and scour morphology around tripod in combined waves and current. The tripod model was made using the 3D printing technology, and it was installed in seabed with three installation angles α = 0°, 90°and 180° respectively. In the present study, the scour evolution and scour characteristic were first analyzed. Then, the equilibrium scour depth Seq was investigated. Furthermore, a parametric study was carried out to study the effects of Froude number Fr and Euler number Eu on equilibrium scour depth Seq respectively. Finally, the effects of tripod’s structural elements on Seq were discussed. The results indicate that the maximum scour hole appeared underneath the main column for installation angle α = 0°, 90° and 180°. The Seq for α = 90° was greater than the case of α = 0° and α = 180°, implying the tripod suffered from more severe scour for α = 90°. When KC was fixed, the dimensionless time scale T* for α = 90° was slightly larger than the case of α = 0° and α = 180° and the T* was linearly correlated with Ucw in the range of 0.347

Shear strength and damage characteristics of compacted expansive soil subjected to wet–dry cycles: a multi-scale study - Kuan Liu; Wanjun Ye; Hongjun Jing (Arabian Journal of Geosciences, 2021)

Effect of dietary Bacillus licheniformis on growth, intestinal health, and resistance to nitrite stress in Pacific white shrimp Litopenaeus vannamei - Ying Fan; Xiaolu Wang; Youhong Wang; Haibin Ye; Xiaoqing Yu; Shuxian Wang; Jing Diao; La Xu; Chunlei Gai; Hongjun Liu; Danping Ma (Aquaculture International, 2021)

Scour Characteristics and Equilibrium Scour Depth Prediction around Umbrella Suction Anchor Foundation under Random Waves - Ruigeng Hu; Hongjun Liu; Hao Leng; Peng Yu; Xiuhai Wang (Journal of Marine Science and Engineering, 2021)
A series of numerical simulation were conducted to study the local scour around umbrella suction anchor foundation (USAF) under random waves. In this study, the validation was carried out firstly to verify the accuracy of the present model. Furthermore, the scour evolution and scour mechanism were analyzed respectively. In addition, two revised models were proposed to predict the equilibrium scour depth Seq around USAF. At last, a parametric study was carried out to study the effects of the Froude number Fr and Euler number Eu for the Seq. The results indicate that the present numerical model is accurate and reasonable for depicting the scour morphology under random waves. The revised Raaijmakers’s model shows good agreement with the simulating results of the present study when KCs,p

Profiling of Serum Exosome MiRNA Reveals the Potential of a MiRNA Panel as Diagnostic Biomarker for Alzheimer’s Disease - Zhiwu Dong; Hongjun Gu; Qiang Guo; Shuang Liang; Jian Xue; Feng Yao; Xianglu Liu; Feifei Li; Huiling Liu; Li Sun; Kewen Zhao (Molecular Neurobiology, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Oxidative Stress and Trace Elements in Pulmonary Tuberculosis Patients During 6 Months Anti-tuberculosis Treatment - Chaoqun Qi; Hongjun Wang; Zhaoying Liu; Haibo Yang (Biological Trace Element Research, 2021)

Impact of different types of environmental regulation on employment scale: an analysis based on perspective of provincial heterogeneity - Wen Guo; Hongjun Dai; Xiaorui Liu (Environmental Science and Pollution Research, 2020)

Without insight accompanied with deteriorated brain functional alterations in healthy individuals with auditory verbal hallucinations: a pilot study - Chuanjun Zhuo; Feng Ji; Xiaodong Lin; Hongjun Tian; Lina Wang; Sha Liu; Hong Sang; Wenqiang Wang; Chunmian Chen (Brain Imaging and Behavior, 2020)
Few studies have reported on brain functional differences between healthy individuals with auditory verbal hallucinations (Hi-AVH) with and without insight, so we designed a study to address this knowledge gap. We enrolled 12 Hi-AVH with insight, 15 Hi-AVH without insight, and 15 AVH-free controls (Healthy controls). Global functional connectivity density (gFCD) mapping was used to estimate brain networks. We found that the most common alterations in both Hi-AVH groups were increased gFCD in superior parietal lobule and superior temporal gyrus. We also found that distinct brain functional patterns of Hi-AVH without insight comprised lower gFCD in the frontal lobe oculomotor area, dorsolateral prefrontal cortex, supramarginal gyrus, primary auditory cortex, sensorimotor cortex, ventral anterior, and posterior cingulate Our pilot findings support the hypothesis that abnormal reciprocal action in the circuits for processing perception, memory, language, and attentional control may be pathological features of auditory verbal hallucinations.

Factors of relevance for improving the uniformity of oxygen distribution in drip irrigation water * - Hongjun Lei; Huan Liu; Ron Balsys; David J. Midmore; Min Zang; Surya Bhattarai (Irrigation and Drainage, 2020)
Aerating water using microbubbles in irrigation for drip and subsurface drip irrigation systems has been reported to produce positive effects on plant growth and yield. However, maintaining the uniformity of bubble distribution in irrigation lines across long‐row configuration is a challenge. Air injection of microbubbles in irrigation water using a gas diffuser (Seair Diffusion System, Model SA75) has a significant gain in dissolved oxygen (DO) distribution over 850 m length of drip tape. Furthermore, with oxygen injection with a Venturi, DO in irrigation water reached as high as 44 ppm and was maintained well above 35 ppm up to a distance of 700 m and did not drop below 20 ppm, even at a distance of 850 m. Pressure compensated emitters recorded significantly higher DO concentrations compared to non‐pressure compensated emitters along the entire length of the irrigation line. Additionally, use of surfactant in irrigation water, up to 4 ppm, resulted in increased gas void fraction and DO concentration compared to the control for both air and oxygen injection irrigation. Highest oxygen saturation was recorded with 4 ppm surfactant, both for air injections (165%) and oxygen injection (438%) treatment along 200 m of non‐pressure compensated drip tape.

Geochemistry and Petrogenesis of Volcanic Rocks from the Continent-Ocean Transition Zone in Northern South China Sea and Their Tectonic Implications - Yue Xu; Yaoming Yang; Hongjun Yu; Wei Gao; Xiangxing Gao; Baohua Liu; Xu Tian; Jichao Yang; Wenquan Zhang (Journal of Ocean University of China, 2020)

High levels of genetic diversity and connectivity of whitespotted conger Conger myriaster in the East China Coast - Congcong Zou; Lijuan Wang; Lingming Kong; Yingjun Wang; Zhihao Wu; Jianhe Xu; Aihuan Song; Hongjun Liu; Feng You (Marine Biodiversity, 2020)

A longitudinal study of brain volume changes in rhesus macaque model infected with SIV - Bonan Song; Yunfang Li; Jiaojiao Liu; Haifeng Mi; Dan Liu; Wei Wang; Jun Sun; Yuanyuan Wang; Hongjun Li (Journal of NeuroVirology, 2020)

Salvianolic acid A attenuated myocardial infarction–induced apoptosis and inflammation by activating Trx - Rui Zhou; Jinhuan Gao; Changpei Xiang; Zhenming Liu; Yi Zhang; Jingjing Zhang; Hongjun Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Advances of Four Machine Learning Methods for Spatial Data Handling: a Review - Peijun Du; Xuyu Bai; Kun Tan; Zhaohui Xue; Alim Samat; Junshi Xia; Erzhu Li; Hongjun Su; Wei Liu (Journal of Geovisualization and Spatial Analysis, 2020)

Magnetic properties indicate the sources of hadal sediments in the Yap Trench, northwest Pacific Ocean - Yu Chen; Jichao Yang; Olusegun A. Dada; Yaomin Yang; Zhen Lin; Zhen Cui; Yue Xu; Hongjun Yu; Baohua Liu (Journal of Oceanology and Limnology, 2020)

Biofertilizer application triggered microbial assembly in microaggregates associated with tomato bacterial wilt suppression - Menghui Dong; Mengli Zhao; Zongzhuan Shen; Xuhui Deng; Yannan Ou; Chengyuan Tao; Hongjun Liu; Rong Li; Qirong Shen (Biology and Fertility of Soils, 2020)

Study on the Influence of Mud Properties on the Stability of Excavated Face of Slurry Shield and the Quality of Filter Cake Formation - Hu Wang; Jian Chen; Hongjun Liu; Lei Guo; Yao Lu; Xiuting Su; Yongmao Zhu; Tao Liu (Journal of Marine Science and Engineering, 2020)
In the construction of subsea tunnels, the stability and control of the excavation surface are the main concerns of the engineering community. In this paper, the Xiamen Metro Line 2 is used as the study case. The filter cake formation of mud shields is experimentally studied, and the excavation surface is numerically simulated. It is found that the formation of filter cake does not require a large pressure difference, and can be formed under 0.06 MPa. With the increase of pressure, the quality of filter cake is further improved, and a small amount of seawater (volume ratio less than 3%) also has a significant effect on the viscosity of mud. Under different cross-section geological conditions, with the decrease of the support pressure of the excavation face, the vertical displacement and vertical (Y-direction) displacement of the excavation face dome gradually increase, the maximum longitudinal displacement is 9.7 mm, the maximum longitudinal displacement can reach 23.9 mm, and the growth trend is nonlinear. According to different stratum conditions, during the excavation of the tunnel, the plastic area of the excavation face is different.

Magnesium alleviates aluminum toxicity by promoting polar auxin transport and distribution and root alkalization in the root apex in populus - Zhen Zhang; Dunyi Liu; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Juanjuan Sun; Longran Chang; Keming Luo; Nannan Li (Plant and Soil, 2020)

Genetic Assessment of a Black Rockfish, Sebastes schlegelii, Stock Enhancement Program in Lidao Bay, China Based on Mitochondrial and Nuclear DNA Analysis - Lijuan Wang; Zhihao Wu; Yingjun Wang; Mengxia Liu; Aihuan Song; Hongjun Liu; Feng You (Frontiers in Marine Science, 2020)

Phylodynamic analysis of two amino acid substitutions in the hemagglutinin protein of canine distemper virus strains detected in fur-bearing animals in China - Rongshan Tao; Hengxing Ba; Jie Chen; Mengjia Liu; Hongjun Pan; Xue Li; Quankai Wang; Jianjun Zhao (Virus Genes, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Wave-Induced Seafloor Instability in the Yellow River Delta: Flume Experiments - Xiuhai Wang; Chaoqi Zhu; Hongjun Liu (Journal of Marine Science and Engineering, 2019)
Geological disasters of seabed instability are widely distributed in the Yellow River Delta, posing a serious threat to the safety of offshore oil platforms and submarine pipelines. Waves act as one of the main factors causing the frequent occurrence of instabilities in the region. In order to explore the soil failure mode and the law for pore pressure response of the subaqueous Yellow River Delta under wave actions, in-lab flume tank experiments were conducted in this paper. In the experiments, wave loads were applied with a duration of 1 hour each day for 7 consecutive days; pore water pressure data of the soil under wave action were acquired, and penetration strength data of the sediments were determined after wave action. The results showed that the fine-grained seabed presented an arc-shaped oscillation failure form under wave action. In addition, the sliding surface firstly became deeper and then shallower with the wave action. Interestingly, the distribution of pores substantially coincided with that of sliding surfaces. For the first time, gas holes were identified along with their positioning and angle with respect to the sediments. The presence of gas may serve as a primer for submarine slope failures. The wave process can lead to an increase in the excess pore pressure, while the anti-liquefaction capacity of the sediments was improved, causing a decrease in the excess pore pressure resulting from the next wave process. Without new depositional sediments, the existing surface sediments can form high-strength formation under wave actions. The test results may provide a reference for numerical simulations and engineering practice.

Enzyme and pH dual-responsive avermectin nano-microcapsules for improving its efficacy - Guanghua Liu; Guanquan Lin; Xida Lin; Hongjun Zhou; Huayao Chen; Li Hao; Xinhua Zhou (Environmental Science and Pollution Research, 2019)

Fine mapping of the wheat powdery mildew resistance gene Pm52 using comparative genomics analysis and the Chinese Spring reference genomic sequence - Peipei Wu; Jinghuang Hu; Jingwei Zou; Dan Qiu; Yunfeng Qu; Yahui Li; Teng Li; Hongjun Zhang; Li Yang; Hongwei Liu; Yang Zhou; Zhongjun Zhang; et al. (Theoretical and Applied Genetics, 2019)

IVIG Delays Onset in a Mouse Model of Gerstmann-Sträussler-Scheinker Disease - Huiying Gu; Yvonne Kirchhein; Timothy Zhu; Gang Zhao; Hongjun Peng; Eileen Du; Junyi Liu; James A. Mastrianni; Martin R. Farlow; Richard Dodel; Yansheng Du (Molecular Neurobiology, 2019)

Control of NOx emissions by air staging in small- and medium-scale biomass pellet boilers - Yuening Li; Yingchao Lin; Jingbo Zhao; Boyang Liu; Ting Wang; Peng Wang; Hongjun Mao (Environmental Science and Pollution Research, 2019)

Altered voxel-wise gray matter structural brain networks in schizophrenia: Association with brain genetic expression pattern - Feng Liu; Hongjun Tian; Jie Li; Shen Li; Chuanjun Zhuo (Brain Imaging and Behavior, 2019)

Threshold effect of the groundwater depth on the photosynthetic efficiency of Tamarix chinensis in the Yellow River Delta - Jiangbao Xia; Jiayun Ren; Ximei Zhao; Fengjuan Zhao; Hongjun Yang; Junhua Liu (Plant and Soil, 2018)

Phytoplankton pigment pattern in the subsurface chlorophyll maximum in the South Java coastal upwelling system, Indonesia - Chunlei Gao; Mingzhu Fu; Hongjun Song; Lei Wang; Qinsheng Wei; Ping Sun; Lin Liu; Xuelei Zhang (Acta Oceanologica Sinica, 2018)

Bearing capacity of offshore umbrella suction anchor foundation in silty soil under varying loading modes - Qi Yang; Guanglai Pan; Hongjun Liu; Quandi Wang (Marine Georesources & Geotechnology, 2018)

Stability analysis of suction bucket foundations under wave cyclic loading and scouring - Xuguang Chen; Tao Liu; Yuke Jiang; Hongjun Liu; Hailei Kou; Jianpeng Xu; Xixi Liu; Jinzhong Liu; Tianchi Ma; Tao Feng; Xiaodong Niu (Marine Georesources & Geotechnology, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Construction and verification of a unified p–y curve for laterally loaded piles - Hongjiang Li; Liyuan Tong; Songyu Liu; Hongjun Liu; Mingfei Zhang (Bulletin of Engineering Geology and the Environment, 2018)

Biochemical and genetic analyses of N metabolism in maize testcross seedlings: 2. Roots - Ignacio Trucillo Silva; Hari Kishan R. Abbaraju; Lynne P. Fallis; Hongjun Liu; Michael Lee; Kanwarpal S. Dhugga (Theoretical and Applied Genetics, 2018)

Continuous application of different organic additives can suppress tomato disease by inducing the healthy rhizospheric microbiota through alterations to the bulk soil microflora - Hongjun Liu; Wu Xiong; Ruifu Zhang; Xinnan Hang; Dongsheng Wang; Rong Li; Qirong Shen (Plant and Soil, 2018)

The impact of modern plant breeding on dominant Chinese wheat cultivars (Triticum aestivum L.) revealed by SSR and functional markers - Lingzhi Meng; Chao Xiang; Hongwei Liu; Li Yang; Chunyan Mai; Liqiang Yu; Yunliang Wei; Hongjie Li; Hongjun Zhang; Yang Zhou (Genetic Resources and Crop Evolution, 2018)

Development and Application of Urban High Temporal-Spatial Resolution Vehicle Emission Inventory Model and Decision Support System - Yi Zhang; Lin Wu; Chao Zou; Boyu Jing; Xiaoyu Li; Tim Barlow; Turpin Kevin; Michel André; Yao Liu; Peipei Ren; Gongdong Wang; Hongjun Mao (Environmental Modeling & Assessment, 2017)

Breeding potential of maize germplasm populations to improve yield and predominant heterotic pattern in Northeast China - Hongjun Yong; Zhenguo Jin; Li Gao; Lin Zhang; Xianjun Liu; Fangjun Zhang; Xiaocong Zhang; Degui Zhang; Mingshun Li; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

Alternative reverse genetics system for influenza viruses based on a synthesized swine 45S rRNA promoter - Kai Wang; Qi Huang; Zhiwei Yang; Kezong Qi; Hongmei Liu; Hongjun Chen (Virus Genes, 2017)

Biochemical and genetic analyses of N metabolism in maize testcross seedlings: 1. Leaves - Ignacio Trucillo Silva; Hari Kishan R. Abbaraju; Lynne P. Fallis; Hongjun Liu; Michael Lee; Kanwarpal S. Dhugga (Theoretical and Applied Genetics, 2017)

De novo assembly, gene annotation, and molecular marker development using Illumina paired-end transcriptome sequencing in the clam Saxidomus purpuratus - Hongjun Li; Min Liu; Sheng Ye; Feng Yang (Genes & Genomics, 2017)

Length-weight, length-length relationships, and condition factors of black rockfish Sebastes schlegelii Hilgendorf, 1880 in Lidao Bay, China - Lijuan Wang; Zhihao Wu; Mengxia Liu; Wei Liu; Wenxi Zhao; Hongjun Liu; Peijun Zhang; Feng You (Thalassas: An International Journal of Marine Sciences, 2017)

Model test and stress distribution law of unsymmetrical loading tunnel in bedding rock mass - Xinrong Liu; Hongjun Chen; Kun Liu; Chunmei He (Arabian Journal of Geosciences, 2017)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

Fine mapping of a quantitative trait locus conferring resistance to maize rough dwarf disease - Changlin Liu; Jinge Hua; Chang Liu; Degui Zhang; Zhuanfang Hao; Hongjun Yong; Chuanxiao Xie; Mingshun Li; Shihuang Zhang; Jianfeng Weng; Xinhai Li (Theoretical and Applied Genetics, 2016)

Synthesis, Aggregation Induced Emission and Mechanochromic Luminescence of New β-Diketone Derivatives Bearing Tetraphenylene Moieties - Haijie Shi; Rui Liu; Senqiang Zhu; Qiqi Gong; Hong Shi; Xiaolin Zhu; Hongjun Zhu (Journal of Fluorescence, 2016)

Geochemical characteristics and accumulated process of heavy crude oil of Chunguang oilfield in Junggar Basin, China - Yuanfang Fan; Lianfu Mei; Hongjun Liu (Journal of Earth Science, 2016)

Numerical Model-Based Artificial Neural Network Model and Its Application for Quantifying Impact Factors of Urban Air Quality - Jianjun He; Ye Yu; Yaochen Xie; Hongjun Mao; Lin Wu; Na Liu; Suping Zhao (Water, Air, & Soil Pollution, 2016)

Distinct Hippocampal Expression Profiles of lncRNAs in Rats Exhibiting a PTSD-like Syndrome - Liu Qingzhen; Ma Jiehua; Yu Zhiyang; Liu Hongjun; Chen Chunlong; Li Weiyan (Molecular Neurobiology, 2016)

Longitudinal assessment of fractional anisotropy alterations caused by simian immunodeficiency virus infection: a preliminary diffusion tensor imaging study - Zhenchao Tang; Enqing Dong; Jiaojiao Liu; Zhenyu Liu; Wenjuan Wei; Bo Wang; Hongjun Li; Jie Tian (Journal of NeuroVirology, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

Genetic and agronomic assessment of cob traits in corn under low and normal nitrogen management conditions - Constantin Jansen; Yongzhong Zhang; Hongjun Liu; Pedro J. Gonzalez-Portilla; Nick Lauter; Bharath Kumar; Ignacio Trucillo-Silva; Juan Pablo San Martin; Michael Lee; Kevin Simcox; Jeff Schussler; Kanwarpal Dhugga; et al. (Theoretical and Applied Genetics, 2015)

Hyperspectral image classification based on volumetric texture and dimensionality reduction - Hongjun Su; Yehua Sheng; Peijun Du; Chen Chen; Kui Liu (Frontiers of Earth Science, 2015)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Grey matter volume abnormalities in patients with bipolar I depressive disorder and unipolar depressive disorder: a voxel-based morphometry study - Yi Cai; Jun Liu; Li Zhang; Mei Liao; Yan Zhang; Lifeng Wang; Hongjun Peng; Zhong He; Zexuan Li; Weihui Li; Shaojia Lu; Yuqiang Ding; et al. (Neuroscience Bulletin, 2015)

Hiding message into DNA sequence through DNA coding and chaotic maps - Guoyan Liu; Hongjun Liu; Abdurahman Kadir (Medical & Biological Engineering & Computing, 2014)

Distribution of phthalate esters in topsoil: a case study in the Yellow River Delta, China - Yang Hongjun; Xie Wenjun; Liu Qing; Liu Jingtao; Yu Hongwen; Lu Zhaohua (Environmental Monitoring and Assessment, 2013)

Breeding potential of U.S. maize germplasm for utilization in Chinese temperate conditions - Hongjun Yong; Xiaocong Zhang; Degui Zhang; Jianjun Wang; Huanxin Zhang; Mingshun Li; Wenguo Liu; Jianfeng Weng; Zhuanfang Hao; Xiaoke Ci; Li Bai; Xinhai Li; et al. (Euphytica, 2013)

Intracellular Cu/Zn superoxide dismutase (Cu/Zn-SOD) from hard clam Meretrix meretrix: its cDNA cloning, mRNA expression and enzyme activity - Xianggang Gao; Chongbo He; Hong Liu; Hongjun Li; Dan Zhu; Shengli Cai; Ying Xia; Ying Wang; Zhe Yu (Molecular Biology Reports, 2012)

Genetic and physical fine mapping of the novel brown midrib gene bm6 in maize (Zea mays L.) to a 180 kb region on chromosome 2 - Yongsheng Chen; Hongjun Liu; Farhad Ali; M. Paul Scott; Qing Ji; Ursula Karoline Frei; Thomas Lübberstedt (Theoretical and Applied Genetics, 2012)

Factors affecting summer maize yield under climate change in Shandong Province in the Huanghuaihai Region of China - Guoqing Chen; Hongjun Liu; Jiwang Zhang; Peng Liu; Shuting Dong (International Journal of Biometeorology, 2012)

Seasonal variability of the zooplankton community in the southwest of the Huanghai Sea (Yellow Sea) Cold Water Mass - Ping Liu; Hongjun Song; Xiao Wang; Zongling Wang; Xinming Pu; Mingyuan Zhu (Acta Oceanologica Sinica, 2012)

Common variant (rs9939609) in the FTO gene is associated with metabolic syndrome - Donghao Zhou; Hongjun Liu; Ming’ai Zhou; Shengxiang Wang; Jingling Zhang; Lin Liao; Fang He (Molecular Biology Reports, 2012)

Development and Linkage Analysis of 104 New Microsatellite Markers for Bay Scallop (Argopecten irradians) - Hongjun Li; Xiao Liu; Guofan Zhang (Marine Biotechnology, 2012)

Identification of Differentially Expressed Genes in Lung Tissues of Nickel-Exposed Rats Using Suppression Subtractive Hybridization - Jing Zhang; Jun Zhang; Yingying Fan; Lihong Liu; Mengjie Li; Yang Zhou; Zhihua Shao; Hongjun Shi; Ying Wang (Biological Trace Element Research, 2011)

Characteristics and causes of the preconsolidation stress of soils in the Yellow River Delta - Xiujuan Yang; Yonggang Jia; Hongjun Liu; Hongxian Shan (Journal of Ocean University of China, 2009)